Cathode for solid secondary battery, and solid secondary battery comprising the same
Patent Information
- Application Number
- KR1020230121174
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-09-12
Smart Images

Figure 112023100869508-PAT00004_ABST
Abstract
Description
Technology Field
[0001] This invention relates to a positive electrode for a solid-state secondary battery and a solid-state secondary battery containing the same. Background Technology
[0002] Recently, driven by industrial demands, the development of batteries with high energy density and safety is actively underway. For example, lithium batteries are used in various applications, including information devices, communication equipment, and automobiles. Since automobiles are a matter of life and death, safety is also critical.
[0003] Lithium batteries using liquid electrolytes may have an increased risk of fire and / or explosion in the event of a short circuit. Solid-state rechargeable batteries employing solid electrolytes instead of liquid electrolytes are being proposed. Solid electrolytes have a lower risk of ignition compared to liquid electrolytes.
[0004] Solid-state secondary batteries can reduce the possibility of fire or explosion by employing a solid electrolyte instead of a liquid electrolyte. Solid-state batteries can provide enhanced safety. The problem to be solved
[0005] One aspect is to provide a positive electrode for a solid-state secondary battery with improved interlayer adhesion.
[0006] Another aspect is to provide a solid-state secondary battery with improved performance including the above-mentioned anode. means of solving the problem
[0007] According to one embodiment
[0008] Positive current collector;
[0009] A positive electrode for a solid secondary battery is provided, comprising: an adhesion binder layer located on a positive electrode current collector and containing an adhesive polymer; and a positive electrode active material layer located on the adhesion binder layer and containing a composite positive electrode active material and a cohesion binder, wherein the composite positive electrode active material comprises a Li2S-containing composite.
[0010] According to another embodiment, a solid secondary battery is provided comprising the anode described above; a cathode; and a solid electrolyte layer disposed between the anode and the cathode. Effects of the invention
[0011] According to one aspect, it is possible to provide a solid secondary battery with improved discharge capacity and rate characteristics through improved adhesion between the substrate and the electrode, and improved lifespan characteristics through stable contact without stable detachment even during repeated shrinkage and expansion during cycling. Brief explanation of the drawing
[0012] FIG. 1 is a cross-sectional view of a solid secondary battery according to an exemplary embodiment. FIG. 2 is a cross-sectional view of a solid secondary battery according to an exemplary embodiment. FIG. 3 is a cross-sectional view of a solid secondary battery according to an exemplary embodiment. FIG. 4 is a cross-sectional view of a solid secondary battery according to an exemplary embodiment. FIG. 5 is a cross-sectional view of a solid secondary battery according to an exemplary embodiment. Specific details for implementing the invention
[0013] Unless otherwise defined, all terms used in this disclosure (including technical and scientific terms) have the same meaning as generally understood by those skilled in the art to which this disclosure pertains. Additionally, terms as defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning within the context of the relevant technology and this disclosure, and should not be interpreted in an idealized or overly formal sense.
[0014] Exemplary embodiments are described in this disclosure with reference to cross-sectional views, which are schematic diagrams of idealized embodiments. As such, variations from the depicted shapes should be expected as a result of, for example, manufacturing techniques and / or tolerances. Accordingly, the embodiments described in this disclosure should not be interpreted as being limited to the specific shapes of the regions as depicted in this disclosure, but should include variations in shapes resulting from, for example, manufacturing. For example, a region depicted or described as flat may typically have rough and / or non-linear features. Furthermore, an angle depicted as sharp may be rounded. Accordingly, the regions depicted in the drawings are essentially schematic, and the shapes are not intended to depict the exact shape of the region and are not intended to limit the scope of the claims.
[0015] The present creative idea may be embodied in many different forms and should not be interpreted as being limited to the embodiments described in this disclosure. Embodiments are provided to ensure that this disclosure is made thorough and complete, and to fully convey the scope of the present creative idea to those skilled in the art. Identical reference numerals denote identical components.
[0016] When it is stated that one component is "on top" of another component, it can be understood that it may be directly on top of the other component or that another component may be interposed between them. In contrast, when it is stated that a component is "directly on top" of another component, no component is interposed between them.
[0017] Terms such as “first,” “second,” “third,” etc., may be used in this disclosure to describe various components, components, regions, layers, and / or zones, but these components, components, regions, layers, and / or zones should not be limited by these terms. These terms are used only to distinguish one component, component, region, layer, or zone from another component, component, region, layer, or zone. Accordingly, the first component, component, region, layer, or zone described below may be referred to as the second component, component, region, layer, or zone without departing from the teachings of this disclosure.
[0018] The terms used in this disclosure are intended to describe specific embodiments only and are not intended to limit the creative idea. Unless the content clearly indicates otherwise, the singular form used herein is intended to include the plural form including “at least one.” “At least one” should not be interpreted as limiting to the singular. As used in this disclosure, the term “and / or” includes any combination of one or more of the listed items. The terms “comprising” and / or “comprising” as used in the detailed description specify the presence of the specified features, regions, integers, steps, actions, components, and / or components, and do not exclude the presence or addition of one or more other features, regions, integers, steps, actions, components, components, and / or groups thereof.
[0019] Spatially relative terms such as "bottom," "lower," "lower," "top," "upper," and "upper" may be used herein to facilitate the description of the relationship of one component or feature to another component or feature. Spatially relative terms are to be understood as intended to include different orientations of the device during use or operation in addition to the orientations depicted in the drawings. For example, if the device in the drawings is inverted, the component described as "bottom" or "lower" of another component or feature will be oriented to the "top" of the other component or feature. Thus, the exemplary term "bottom" may encompass both the upper and lower directions. The device may be positioned in different directions (it may be rotated 90 degrees or rotated in other directions), and the spatially relative terms used in this disclosure may be interpreted accordingly.
[0020] "Group" refers to a group of elements in the periodic table according to the International Union of Pure and Applied Chemistry ("IUPAC") group classification system of groups 1-18.
[0021] In the present disclosure, "particle size" or "particle diameter" refers to the average diameter when the particles are spherical and the average major axis length when the particles are non-spherical. The particle diameter can be measured using a particle size analyzer (PSA). "Particle size" or "particle diameter" is, for example, the average particle diameter. The "average particle diameter" is, for example, D50, the median particle diameter.
[0022] D50 is the particle size corresponding to 50% of the cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0023] D90 is the particle size corresponding to the 90% cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0024] D10 is the particle size corresponding to the 10% cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0025] In the present disclosure, “metal” includes both metals and metalloids such as silicon and germanium in an elemental or ionic state.
[0026] In this disclosure, "alloy" means a mixture of two or more metals.
[0027] In the present disclosure, "electrode active material" refers to an electrode material capable of undergoing lithiation and delithiation.
[0028] In the present disclosure, "anode active material" refers to an anode material capable of undergoing lithiation and delithiation.
[0029] In the present disclosure, "anode active material" refers to an anode material capable of undergoing lithiation and delithiation.
[0030] In the present disclosure, "lithiation" and "to lithiate" refer to the process of adding lithium to an electrode active material.
[0031] In the present disclosure, "delithiation" and "to delithiate" refer to the process of removing lithium from an electrode active material.
[0032] In this disclosure, "charge" and "to charge" refer to the process of providing electrochemical energy to a battery.
[0033] In this disclosure, "discharge" and "discharge" refer to the process of removing electrochemical energy from a battery.
[0034] In this disclosure, "anode" and "cathode" refer to electrodes where electrochemical reduction and lithiation occur during the discharge process.
[0035] In this disclosure, "cathode" and "anode" refer to electrodes where electrochemical oxidation and delithiation occur during the discharge process.
[0036] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not currently anticipated or cannot be anticipated may arise to the applicant or those skilled in the art. Accordingly, the appended claims, which may be filed and modified, are intended to include all such alternatives, modifications, variations, improvements, and substantial equivalents.
[0038] A positive electrode for a solid secondary battery according to exemplary embodiments, a solid secondary battery including the same, and a method for manufacturing the same will be described in more detail below.
[0039] [anode]
[0040] A positive electrode for a solid secondary battery according to one embodiment comprises: a positive electrode current collector; an adhesive binder layer located on the positive electrode current collector and containing an adhesive polymer; and a positive electrode active material layer located on the adhesive binder layer and containing a composite positive electrode active material and a cohesion binder, wherein the composite positive electrode active material comprises a Li2S-containing composite.
[0041] In order to prevent detachment from the substrate due to shrinkage and expansion during charging and discharging and to improve electron conductivity, it is necessary to strengthen the adhesion between the substrate and the lithium sulfide active material electrode and the substrate for a positive electrode for a solid secondary battery using lithium sulfide as a positive electrode active material.
[0042] Accordingly, the present disclosure provides an anode that exhibits excellent electrochemical characteristics without surface detachment from the substrate even under repeated shrinkage and expansion due to charging and discharging by forming an adhesive binder layer between the anode active material layer containing a Li2S-containing composite and the substrate to improve adhesion between the two and reduce interfacial resistance, and by utilizing the anode active material layer containing the adhesive binder.
[0043] The above composite cathode active material is a Li2S-containing composite, which comprises a composite of Li2S and a lithium salt; and a sulfide-based solid electrolyte.
[0044] The above-mentioned complex of Li2S and lithium salt is Li2S-Li a X b It is represented as (1≤a≤5, 1≤b≤5), where X is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF6, BF4, SbF6, AsF6, ClO4, AlO2, AlCl4, NO3, CO3, BH4, SO4, BO3, PO4, NCl, NCl2, BN2, or a combination thereof.
[0045] In solid-state secondary batteries utilizing lithium sulfide as the cathode active material, lithium sulfide is an insulator with almost no electrical or ionic conductivity; therefore, it is required to be composited with materials that possess high electrical and ionic conductivity. Furthermore, due to the expansion and contraction during charging and discharging of lithium sulfide-containing batteries, the cathode active material detaches from the cathode current collector, leading to a decrease in electron conductivity; thus, improvements are required to address this issue.
[0046] Accordingly, the anode of the present disclosure utilizes a Li2S-containing composite as the anode active material and forms an adhesive binder layer containing an adhesive polymer between the anode current collector and the anode active material layer, and uses an adhesive binder on the anode active material layer to further lower the interfacial resistance between the anode active material layer and the anode current collector, thereby effectively suppressing the problem of degradation of the sulfide-based solid electrolyte contained in the anode active material layer during battery operation.
[0047] The formation of the above adhesive binder layer can effectively prevent the deterioration of the sulfide-based solid electrolyte in the positive active material layer, improve the adhesion of the positive electrode, and reduce the interfacial resistance between the positive current collector and the positive active material layer.
[0048] The thickness of the adhesive binder layer according to one embodiment may be 5 nm to 1 μm, 5 nm to 800 nm, 5 nm to 500 nm, 5 nm to 400 nm, 5 nm to 300 nm, 10 nm to 300 nm, 10 nm to 100 nm, or 10 nm to 50 nm.
[0049] According to another embodiment, the thickness of the adhesive binder layer is 20 nm to 1 μm, 20 nm to 800 nm, 20 nm to 500 nm, 20 nm to 300 nm, or 20 nm to 100 nm. By being formed within this thickness range, the sulfide-based solid electrolyte contained in the anode active material layer can be effectively protected while lowering the interfacial resistance.
[0050] The adhesive polymer constituting the adhesive binder layer is one or more selected from, for example, polydopamine, cation-substituted polycarboxylic acids and copolymers thereof, poly(norepinephrin), poly(meth)acrylamide, polyvinyl alcohol, poly(2-hydroxymethyl(meth)acrylate), methyl(meth)acrylate-(meth)acrylic acid copolymer, polymethyl(meth)acrylate, poly(meth)acrylic acid), and styrene-(meth)acrylic acid copolymer.
[0051] The above-mentioned cation-substituted polycarboxylic acid and its copolymer have one cation selected from lithium ions (Li+), sodium ions (Na+), potassium ions (K+), and ammonium ions (NH4+). Polycarboxylic acid refers to a polymer formed by the polymerization of various types of monomers containing one or more monomers having one or more carboxyl groups (-COOH), and has a weight-average molecular weight of 1,000 to 1,000,000. Examples of such polycarboxylic acids include polyacrylic acid, polymethacrylic acid, and polymaleic acid. The cation-substituted polycarboxylic acid is a substance in which the hydrogen of such polycarboxylic acid is substituted with a cation, and includes, for example, one or more selected from lithium polyacrylate (LiPAA) and lithium polymethacrylate.
[0052] Cation-substituted polycarboxylic acid copolymers are copolymers containing monomer repeating units corresponding to cation-substituted polycarboxylic acids, and examples of such copolymers include poly(acrylic acid-co-maleic acid) lithium salt, poly(methylvinyl ether-alt-maleic acid) lithium salt, or poly(butadiene-co-maleic acid) lithium salt.
[0053] One or more glass transition temperatures selected from cation-substituted polycarboxylic acids and copolymers thereof are 50°C or higher, for example, 50 to 200°C, specifically 50 to 150°C. Also, one or more melting points selected from cation-substituted polycarboxylic acids and copolymers thereof are 100°C or higher, for example, in the range of 100 to 300°C, specifically 100 to 200°C. When an intermediate layer is formed using cation-substituted polycarboxylic acids and copolymers having such glass transition temperatures and melting points, the intermediate layer maintains its shape at the battery operating temperature (for example, 0 to 90°C), and the likelihood of inflow into the intermediate layer is small. One or more selected from the above cation-substituted polycarboxylic acid and its copolymers have a weight-average molecular weight of 1,000 to 1,000,000 and a degree of polymerization of 10 to 1500, for example, 14 to 1400.
[0054] Examples of cation-substituted polycarboxylic acids include lithium polyacrylate.
[0055] The above adhesive binder is polytetrafluoroethylene, polyvinylidene fluoride (PVdF)-based resin, styrene-butadiene rubber (SBR), polyethylene glycol (PEG), polypropylene glycol (PPG), toluene diisocyanate (TDI), polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, It is cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, or a combination thereof. The content of the adhesive binder is 0.5 to 10 parts by weight, 0.5 to 8 parts by weight, 0.5 to 5 parts by weight, 0.6 to 3 parts by weight, 0.7 to 2 parts by weight, or 0.8 to 1 part by weight, based on 100 parts by weight of the total weight of the positive electrode active material layer.The content of the adhesive binder is 5 parts by weight, and the content of the adhesive binder is 100 to 1000 parts by weight, 150 to 950 parts by weight, 200 to 900 parts by weight, 250 to 850 parts by weight, 300 to 800 parts by weight, 350 to 750 parts by weight, 400 to 700 parts by weight, or 450 to 650 parts by weight, based on 100 parts by weight of the adhesive polymer of the adhesive binder layer. If the content of the adhesive binder is greater than the above range, the content of the lithium-sulfur complex in the positive electrode active material layer is relatively reduced, which may result in a decrease in capacity characteristics, and if the content of the adhesive binder is less than the above range, the adhesive strength of the positive electrode active material layer may be reduced.
[0056] The aforementioned anode is equipped with an adhesive binder layer, which not only improves the adhesion between the current collector and the anode active material layer but also enhances stability and reliability against mechanical deformation, such as bending, thereby improving battery performance. Therefore, in a solid-state secondary battery using a cathode containing lithium sulfide as the active material, it is possible to prevent the phenomenon of active material detaching from the surface of the current collector due to changes in the volume of the silicon active material, and to realize a high-capacity solid-state secondary battery in which battery performance is degraded by the increase in interfacial resistance between the current collector and the anode active material layer by forming an adhesive binder layer.
[0057] Li2S-containing complexes include, for example, complexes of Li2S and lithium salts.
[0058] The composite of Li2S and lithium salt possesses ductility, distinguishing it from conventional oxide-based solid electrolytes that are brittle, such as garnet-structured oxide-based solid electrolytes. The composite of Li2S and lithium salt possesses lithium ion conductivity, distinguishing it from conventional lithium-free metal oxides that do not possess lithium ion conductivity, such as alumina. The composite of Li2S and lithium salt is, for example, the result of mechanical milling of Li2S and lithium salt. The composite of Li2S and lithium salt is, for example, the result of a mechanochemical reaction between Li2S and lithium salt, distinguishing it from a simple mixture of Li2S and lithium salt. A simple mixture of Li2S and lithium salt provides high interfacial resistance because it fails to maintain a dense interface between Li2S and lithium salt, which can consequently increase the internal resistance of the solid electrolyte separator.
[0059] The complex of Li2S and lithium salt is Li2S-Li a X bIt is denoted as (1≤a≤5, 1≤b≤5). X is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF6, BF4, SbF6, AsF6, ClO4, AlO2, AlCl4, NO3, CO3, BH4, SO4, BO3, PO4, NCl, NCl2, BN2, or a combination thereof. a is, for example, 1, 2, 3, 4, or 5. b is, for example, 1, 2, 3, 4, or 5. The lithium salt is, for example, a compound that does not contain sulfur (S). The lithium salt may be, for example, a binary compound or a ternary compound. The lithium salt may be, for example, a binary compound composed of lithium and one element selected from Groups 13 through 17 of the periodic table. The lithium salt may be a ternary compound composed of, for example, lithium and two elements selected from Groups 13 to 17 of the periodic table. The binary compound may include, for example, LiI, LiBr, LiCl, LiF, LiH, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, Li3Al2, LiB3, or a combination thereof. The ionic conductivity of the complex may be further enhanced by the inclusion of such binary compounds. The internal resistance of the anode may be further reduced by the inclusion of such a complex in the solid electrolyte separator. Consequently, the cycle characteristics of a solid secondary battery containing such an anode may be further improved. The ternary compound may include, for example, Li3OCl, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiNO3, Li2CO3, LiBH4, Li2SO4, Li3BO3, Li3PO4, Li4NCl, Li5NCl2, Li3BN2, or a combination thereof. The ionic conductivity of the complex may be further enhanced by the inclusion of such ternary compounds in the complex.The internal resistance of the anode can be further reduced by including such a composite. Consequently, the cycle characteristics of a solid secondary battery including such a solid electrolyte separator can be further improved.
[0060] The above composite may further include a carbon-based material. The composite is a composite of Li2S, a lithium salt, and a carbon-based material.
[0061] Carbon-based materials may be any material containing carbon atoms, for example, used as a conductive material in the relevant technical field. Carbon-based materials may be, for example, crystalline carbon, amorphous carbon, or a combination thereof. Carbon-based materials may be, for example, a calcined product of a carbon precursor. Carbon-based materials may be, for example, carbon nanostructures. Carbon nanostructures may be, for example, one-dimensional carbon nanostructures, two-dimensional carbon nanostructures, three-dimensional carbon nanostructures, or a combination thereof. Carbon nanostructures may be, for example, carbon nanotubes, carbon nanofibers, carbon nanobelts, carbon nanorods, graphene, or a combination thereof. Carbon-based materials may be, for example, porous carbon-based materials or non-porous carbon-based materials. Porous carbon-based materials may include, for example, periodic and regular two-dimensional or three-dimensional pores. Porous carbon-based materials include, for example, carbon black such as Ketjen black, acetylene black, Denka black, thermal black, channel black, etc.; It may be graphite, activated carbon, or a combination thereof. The form of the carbon-based material may be, for example, in particle form, sheet form, flake form, etc., but is not limited thereto; any form used as a carbon-based material in the relevant technical field is acceptable. The content of the carbon-based material included in the composite of Li2S, a lithium salt, and a carbon-based material may be, for example, 1 to 20 wt%, 5 to 20 wt%, or 10 to 20 wt% of the total weight of the composite. If the content of the carbon-based material increases excessively, the energy density of the dry cathode film and the all-solid-state secondary battery may decrease. If the content of the carbon-based material decreases excessively, the electronic conductivity of the composite of Li2S, a lithium salt, and a carbon-based material decreases, and the internal resistance of the dry cathode film may increase. Consequently, the cycle characteristics of the all-solid-state secondary battery may deteriorate.
[0062] The Mohs hardness of the lithium salt and the carbon-based material may each be greater than that of Li2S. The Mohs hardness of Li2S is, for example, 0.6 or less. The Mohs hardness of the lithium salt may be 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.5 or more, or 2.0 or more. Since the lithium salt has a Mohs hardness within this range, the grinding of Li2S can be performed more easily during the milling process, and a solid solution of Li2S and the lithium salt can be formed more easily. The Mohs hardness of LiI is, for example, 2.0. The Mohs hardness of the carbon-based material may each be 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.2 or more, or 1.5 or more. Since carbon-based materials have a Mohs hardness in this range, the grinding of Li2S can be performed more easily during the milling process, and composites of Li2S, lithium salts, and carbon-based materials can be formed more easily. The Mohs hardness of carbon nanofibers (CNF) is, for example, 1.5.
[0063] The carbon-based material may include, for example, a fibrous carbon-based material. By including a fibrous carbon-based material in the composite of Li2S, lithium salt, and carbon-based material, the electronic conductivity of the composite of Li2S, lithium salt, and carbon-based material can be further enhanced. By including a fibrous carbon-based material in the composite of Li2S, lithium salt, and carbon-based material, electronic conduction from the surface to the interior of the composite of Li2S, lithium salt, and carbon-based material can be performed more easily. The internal resistance of the dry cathode film containing the composite of Li2S, lithium salt, and carbon-based material is reduced, and the cycle characteristics of the all-solid-state secondary battery containing the dry cathode film can be further improved.
[0064] The aspect ratio of the fibrous carbon-based material may be, for example, 2 or more, 3 or more, 4 or more, 5 or more, 10 or more, or 20 or more. The aspect ratio of the fibrous carbon-based material may be, for example, 2 to 30, 3 to 30, 4 to 30, 5 to 30, 10 to 30, or 20 to 30. The aspect ratio of the fibrous carbon-based material may be, for example, 2 to 30, 2 to 20, 2 to 10, 2 to 8, 2 to 5, or 2 to 4. By having the fibrous carbon-based material have an aspect ratio within this range, the overall electronic conductivity of the composite of Li2S, lithium salt, and carbon-based material is improved, and the local imbalance in electronic conductivity within the composite of Li2S, lithium salt, and carbon-based material can be further alleviated.
[0065] Fibrous carbon-based materials may include, for example, carbon nanostructures. Carbon nanostructures may include, for example, carbon nanofibers (CNF), carbon nanotubes (CNT), carbon nanobelts, carbon nanorods, or combinations thereof.
[0066] Carbon nanostructures can form a primary carbon nanostructure composed of a single carbon nanostructure and a secondary carbon nanostructure composed of multiple aggregated carbon nanostructures.
[0067] The diameter of the primary carbon nanostructure may be, for example, 1 nm to 200 nm, 1 nm to 150 nm, 1 nm to 100 nm, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 20 nm. The length of the primary carbon nanostructure may be, for example, 10 nm to 2 µm, 10 nm to 1.5 µm, 10 nm to 1 µm, 10 nm to 500 nm, 10 nm to 400 nm, 10 nm to 300 nm, 10 nm to 200 nm, or 10 nm to 100 nm. The diameter and length of the primary carbon nanostructure may be measured from scanning electron microscope (SEM) or transmission electron microscope (TEM) images. Alternatively, the diameter and / or length of the primary carbon nanostructure may be measured by laser diffraction.
[0068] A secondary carbon nanostructure is a structure formed by assembling, for example, primary carbon nanostructures to form a bundle or rope type, either wholly or partially. The secondary carbon nanostructure may include, for example, bundle-type carbon nanostructures, rope-type carbon nanostructures, or a combination thereof. The diameter of the secondary carbon nanostructure may be, for example, 2 nm to 200 nm, 3 nm to 150 nm, 5 nm to 100 nm, 5 nm to 50 nm, 5 nm to 30 nm, or 5 nm to 20 nm. The length of the secondary carbon nanotube structure may be, for example, 20 nm to 2 µm, 30 nm to 1.5 µm, 50 nm to 1 µm, 50 nm to 500 nm, 50 nm to 400 nm, 50 nm to 300 nm, 50 nm to 200 nm, or 50 nm to 100 nm. The diameter and length of the secondary carbon nanostructure can be measured from scanning electron microscope (SEM) images or optical microscopes. Alternatively, the diameter and / or length of the secondary carbon nanostructure can be measured by laser diffraction. The secondary carbon nanostructure can be converted into a primary carbon nanostructure by dispersing it in a solvent, for example, and then used to manufacture a composite of Li2S, a lithium salt, and a carbon-based material.
[0069] A composite of Li2S and a lithium salt, or a composite of Li2S, a lithium salt, and a carbon-based material, may include, for example, a solid solution of Li2S and a lithium salt. By including a solid solution of Li2S and a lithium salt in the composite, the ionic conductivity of the composite may be increased. For example, by including lithium ions disposed within the Li2S crystallites in the solid solution of Li2S and a lithium salt, the ionic conductivity of the solid solution of Li2S and a lithium salt may be improved compared to the ionic conductivity of Li2S. Consequently, the ionic conductivity of the composite may be improved and the internal resistance of the composite may be reduced. By including such a composite in the cathode, the internal resistance of the cathode may be further reduced. Consequently, the cycle characteristics of a solid-state secondary battery containing such a cathode may be further improved.
[0070] The size of Li2S crystallites obtained from the XRD spectrum of a composite of Li2S and a lithium salt, or a composite of Li2S, a lithium salt, and a carbon-based material, may be, for example, 20 nm or less, 15 nm or less, or 10 nm or less. The size of Li2S crystallites obtained from the XRD spectrum of the composite may be, for example, 1 to 20 nm, 1 to 15 nm, or 3 to 10 nm. As the size of the Li2S crystallites decreases, the contact area between Li2S and the lithium salt may be further increased. As the contact area between Li2S and the lithium salt is further increased, the ionic conductivity of the composite of Li2S and the lithium salt may be further increased. As the cathode includes such a composite, the internal resistance of the cathode may be further reduced. Consequently, the cycle characteristics of a solid-state secondary battery including such a cathode may be further improved.
[0071] Since Li2S has low ionic conductivity, a composite with a lithium salt is formed to overcome this disadvantage. A composite of Li2S and a lithium salt, or of Li2S, a lithium salt, and a carbon-based material, can provide improved ionic conductivity compared to Li2S alone. The content of Li2S in the composite may be 50 to 95 wt%, 50 to 90 wt%, 50 to 80 wt%, or 50 to 70 wt% of the total weight of the composite of Li2S and the lithium salt. By having the composite with a Li2S content within this range, a cathode with improved ionic conductivity and durability can be manufactured. The content of the lithium salt in the composite of Li2S and the lithium salt may be 5 to 50 wt%, 10 to 50 wt%, 20 to 50 wt%, or 30 to 50 wt% of the total weight of the composite of Li2S and the lithium salt.
[0072] The molar ratio of Li2S to lithium salt in the composite may be, for example, 50:50 to 95:5, 60:40 to 95:5, 60:40 to 90:10, 65:35 to 90:10, 65:35 to 85:15, or 70:30 to 85:15. The molar ratio of Li2S to lithium salt in the composite may be, for example, 50:50 to 95:5, 50:50 to 90:10, 50:50 to 85:15, 50:50 to 80:20, 50:50 to 75:25, or 50:50 to 70:30. By having the molar ratio of Li2S and lithium salt within these ranges, the cycle characteristics of a lithium battery containing the composite cathode active material can be further improved. If the molar ratio of Li2S is excessively high, the effect of improving ion conductivity by the lithium salt may be negligible. If the molar ratio of Li2S is excessively high, the energy density of a lithium battery containing a composite cathode active material may decrease.
[0073] The Mohs hardness of the lithium salt and the carbon-based material may each be greater than that of Li2S. The Mohs hardness of Li2S is, for example, 0.6 or less. The Mohs hardness of the lithium salt may be 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.5 or more, or 2.0 or more. Since the lithium salt has a Mohs hardness within this range, the grinding of Li2S can be performed more easily during the milling process, and a solid solution of Li2S and the lithium salt can be formed more easily. The Mohs hardness of LiI is, for example, 2.0. The Mohs hardness of the carbon-based material may each be 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.2 or more, or 1.5 or more. Since carbon-based materials have a Mohs hardness in this range, the grinding of Li2S can be performed more easily during the milling process, and composites of Li2S, lithium salts, and carbon-based materials can be formed more easily. The modal hardness of carbon nanofibers (CNF) is, for example, 1.5.
[0074] In a composite of Li2S, a lithium salt, and a carbon-based material, the content of the lithium salt may be, for example, 1 to 40 wt%, 5 to 35 wt%, 10 to 35 wt%, 15 to 35 wt%, 20 to 35 wt%, or 25 to 35 wt% of the total weight of the composite of Li2S, a lithium salt, and a carbon-based material. If the content of the lithium salt increases excessively, the energy density of the all-solid-state secondary battery may decrease. If the content of the lithium salt is excessively low, the ionic conductivity of the composite of Li2S, a lithium salt, and a carbon-based material decreases, and the internal resistance of the dry cathode film may increase. Consequently, the cycle characteristics of the all-solid-state secondary battery containing the dry cathode film may deteriorate.
[0075] In a composite of Li2S, a lithium salt, and a carbon-based material, the molar ratio of Li2S to the lithium salt may be, for example, 50:50 to 95:5, 60:40 to 95:5, 60:40 to 90:10, 65:35 to 90:10, 65:35 to 85:15, or 70:30 to 85:15. In a composite of Li2S, a lithium salt, and a carbon-based material, the molar ratio of Li2S to the lithium salt may be, for example, 50:50 to 95:5, 50:50 to 90:10, 50:50 to 85:15, 50:50 to 80:20, 50:50 to 75:25, or 50:50 to 70:30. The cycle characteristics of a solid-state secondary battery containing a dry cathode film can be further improved by having Li2S and lithium salt in this range of molar ratios. If the molar ratio of Li2S is excessively high, the effect of improving ion conductivity by the lithium salt may be negligible. If the molar ratio of Li2S is excessively high, the energy density of a solid-state secondary battery containing a composite cathode active material may decrease.
[0076] The ionic conductivity of a composite of Li2S and a lithium salt, or a composite of Li2S, a lithium salt, and a carbon-based material, is, for example, 1×10⁻⁶ at 25°C. -5 S / cm or more, 2×10 -5 S / cm or more, 4×10 -5 S / cm or more, 6×10 -5 S / cm or more, 8×10 -5 S / cm or more, or 1×10 -4 It can be greater than S / cm. Ionic conductivity can be measured using, for example, electrochemical impedance spectrometry or the DC polarization method. Since the complex of Li2S and lithium salt has ionic conductivity within this range, the internal resistance of the cathode containing the complex of Li2S and lithium salt can be further reduced. The cycle characteristics of the solid-state secondary battery containing the cathode can be improved.
[0077] The Li2S-containing complex may further include a solid electrolyte. The solid electrolyte may further include a sulfide-based solid electrolyte.
[0078] The content of the complex of Li2S and lithium salt may be, for example, 0.1 to 20 wt%, 0.5 to 20 wt%, 0.5 to 15 wt%, 0.5 to 10 wt%, or 1 to 5 wt% of the total weight of the complex of Li2S and lithium salt and the sulfide-based solid electrolyte. The content of the complex of Li2S and lithium salt may be, for example, 0.1 to 20 wt%, 0.5 to 20 wt%, 0.5 to 15 wt%, 0.5 to 10 wt%, or 1 to 5 wt% of the total weight of the anode. By having the anode with a complex content of Li2S and lithium salt within these ranges, the durability of the anode can be further improved and the internal resistance can be further reduced. If the content of the complex of Li2S and lithium salt is excessively low, the effect may be negligible. If the content of the complex of Li2S and lithium salt increases excessively, the internal resistance of the anode may increase.
[0079] The cathode active material layer may include, for example, composite particles of Li2S and lithium salt and sulfide-based solid electrolyte particles. The size of the composite particles of Li2S and lithium salt may be, for example, smaller than the size of the sulfide-based solid electrolyte particles. The size of the composite particles of Li2S and lithium salt may be, for example, 90% or less, 80% or less, 60% or less, 40% or less, 20% or less, or 10% or less of the size of the sulfide-based solid electrolyte particles. The composite particles of Li2S and lithium salt may be placed, for example, in the voids between multiple sulfide-based solid electrolytes. By placing the composite particles of Li2S and lithium salt in the voids between multiple sulfide-based solid electrolytes, the formation of pinholes within the cathode is suppressed, and the internal resistance of the cathode may be reduced. Consequently, the durability of the cathode may be improved.
[0080] The size of the sulfide-based solid electrolyte particles may be, for example, 1 to 10 μm, 1 to 8 μm, 1 to 6 μm, 1 to 5 μm, or 1 to 3 μm. The durability of the anode can be further improved by the sulfide-based solid electrolyte particles having a size within this range. The size of the sulfide-based solid electrolyte particles can be measured using, for example, laser diffraction, scanning electron microscopy, etc. The size of the sulfide-based solid electrolyte particles is, for example, the arithmetic mean value of the particle diameters of a plurality of particles measured using software in a scanning electron microscopy image. The size of the Li2S-containing composite particles, which are the composite anode active material, may be, for example, 10 μm or less, 8 μm or less, 5 μm or less, 2 μm or less, 1.5 μm or less, or 1 μm or less. The size of the composite particles may be, for example, 1 to 10 μm, 2 to 10 μm, 2 to 8 μm, or 3 to 8 μm. The size of the composite particles may be, for example, 0.1 to 10 μm, 0.1 to 8 μm, 0.1 to 5 μm, 0.1 to 2 μm, 0.1 to 1.5 μm, or 0.1 to 1 μm or less. Since the volume change during charging and discharging is suppressed by the composite particles having a size within this range, the degradation of the composite cathode active material containing the composite during charging and discharging can be suppressed. If the size of the composite particles increases excessively, the degradation of the composite cathode active material containing the composite may be accelerated due to the increased volume change of the composite during charging and discharging. Consequently, the cycle characteristics of the solid secondary battery containing such a composite cathode active material may be degraded.
[0081] The size of the Li2S particles included in the composite cathode active material, that is, the size of the Li2S particles included in the composite, may be, for example, 2 μm or less, 1.5 μm or less, or 1 μm or less. The size of the Li2S particles may be, for example, 0.1 to 2 μm, 0.1 to 1.5 μm, or 0.1 to 1 μm or less. By having the composite particles within this range of sizes, they can be more easily placed in the voids between multiple sulfide-based solid electrolytes, the formation of pinholes within the cathode can be suppressed, and the internal resistance of the cathode can be reduced. As a result, the durability of the cathode can be improved.
[0082] The size of the Li2S-containing composite particles can be measured using, for example, laser diffraction or scanning electron microscopy. The size of the Li2S-containing composite is, for example, the arithmetic mean of the particle diameters of multiple particles measured using software from a scanning electron microscope image.
[0083] The ratio of the size of the sulfide-based solid electrolyte particles to the size of the Li2S-containing composite particles may be, for example, 2:1 to 200:1, 2:1 to 100:1, or 2:1 to 50:1. By having a ratio within this range of sizes, the formation of defects in the anode can be suppressed, thereby further improving the durability of the anode. If the ratio of the size of the sulfide-based solid electrolyte particles to the size of the Li2S-containing composite particles is excessively small, the porosity of the anode may increase excessively, which may reduce the durability of the anode. If the ratio of the size of the sulfide-based solid electrolyte particles to the size of the Li2S-containing composite particles is excessively large, it may be difficult to achieve uniform dispersion of the Li2S-containing composite particles within the anode.
[0084] By using a cathode containing the aforementioned composite, it is not necessary to use a lithium metal anode as the cathode, thereby enabling the use of a cathode-free solid secondary battery and providing a solid secondary battery with improved energy density. Furthermore, by including this composite in the composite cathode active material, the cycle characteristics of the solid secondary battery containing the composite cathode active material can be improved. For example, the rate capability of the secondary battery containing such a composite cathode active material can be improved.
[0085] The solid electrolyte in the positive electrode active material layer may be, for example, a sulfide-based solid electrolyte. The solid electrolyte contained in the positive electrode may be the same as or different from the solid electrolyte contained in the electrolyte layer. The solid electrolyte contained in the positive electrode active material layer may have a smaller D50 average particle size compared to the solid electrolyte contained in the electrolyte layer. For example, the D50 average particle size of the solid electrolyte contained in the positive electrode active material layer may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 20% or less of the D50 average particle size of the solid electrolyte contained in the electrolyte layer. The D50 average particle size is, for example, the median particle diameter (D50). The median particle diameter (D50) is the particle size corresponding to 50% of the cumulative volume calculated from the side of the particle having a small particle size in the particle size distribution measured, for example, by laser diffraction.
[0086] A solid electrolyte may be included in an amount of 10 to 60 parts by weight, 10 to 50 parts by weight, 20 to 50 parts by weight, or 30 to 50 parts by weight per 100 parts by weight of the positive electrode active material layer.
[0087] [Solid-state secondary battery]
[0088] A solid secondary battery according to one embodiment comprises a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises the positive electrode described above.
[0089] Referring to FIGS. 1 to 5, a solid secondary battery (1) comprises a positive electrode (10); a negative electrode (20); and a solid electrolyte layer (30) disposed between the positive electrode (10) and the negative electrode (20). The positive electrode (10) comprises a positive electrode according to one embodiment.
[0090] [anode]
[0091] [Anode: Anode active material]
[0092] Referring to FIGS. 1 to 5, the positive electrode (10) comprises a positive electrode current collector (11); an adhesive binder layer (13) disposed on one or both sides of the positive electrode current collector (11) and a positive electrode active material layer (12) located thereon. The positive electrode active material layer (12) comprises a Li2S-containing composite as the positive electrode active material.
[0093] The positive active material layer (12) may additionally include other positive active materials in addition to the composite positive active material described above.
[0094] Other cathode active materials may include, for example, Li2S-containing composites. The Li2S-containing composites include, for example, a composite of Li2S and carbon, a composite of Li2S, carbon, and a solid electrolyte, a composite of Li2S and a solid electrolyte, a composite of Li2S, a lithium salt, and carbon, a composite of Li2S and a metal carbide, a composite of Li2S, carbon, and a metal carbide, a composite of Li2S and a metal nitride, a composite of Li2S, carbon, and a metal nitride, or a combination thereof.
[0095] The composite of Li2S and carbon contains carbon. The carbon may be any material containing carbon atoms, for example, used as a conductive material in the relevant art. The carbon may be, for example, crystalline carbon, amorphous carbon, or a combination thereof. The carbon may be, for example, a calcined product of a carbon precursor. The carbon may be, for example, a carbon nanostructure. The carbon nanostructure may be, for example, a one-dimensional carbon nanostructure, a two-dimensional carbon nanostructure, a three-dimensional carbon nanostructure, or a combination thereof. The carbon nanostructure may be, for example, a carbon nanotube, a carbon nanofiber, a carbon nanobelt, a carbon nanorod, graphene, graphene oxide (GO), reduced graphene oxide (rGO), a graphene ball (GB), or a combination thereof. The carbon may be, for example, porous carbon or non-porous carbon. Porous carbon may contain, for example, periodic and regular two-dimensional or three-dimensional pores. Porous carbon may be, for example, carbon black such as Ketjen black, acetylene black, Denka black, thermal black, channel black, etc. It may be graphite, activated carbon, or a combination thereof. The form of carbon may be, for example, in particle form, sheet form, flake form, etc., but is not limited thereto; any form of carbon used in the relevant technical field is possible. The method for manufacturing the Li2S and carbon composite may be a dry method, a wet method, or a combination thereof, but is not limited thereto; and the method for manufacturing the Li2S and carbon composite in the relevant technical field may be, for example, milling, heat treatment, deposition, etc., but is not necessarily limited thereto; any method used in the relevant technical field is possible.
[0096] The composite of Li2S, carbon, and solid electrolyte comprises carbon and a solid electrolyte. Carbon refers to the composite of Li2S and carbon described above. The solid electrolyte may be, for example, an amorphous solid electrolyte, any material used as an ion-conducting material in the art. The solid electrolyte is, for example, an inorganic solid electrolyte. The solid electrolyte is, for example, a crystalline solid electrolyte, an amorphous solid electrolyte, or a combination thereof. The solid electrolyte is, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or a combination thereof. The sulfide-based solid electrolyte comprises, for example, Li, S, and P, and may optionally further comprise halogen elements. The sulfide-based solid electrolyte may be selected from among sulfide-based solid electrolytes used in the solid electrolyte layer. The sulfide-based solid electrolyte is, for example, 1 × 10⁻⁶ at room temperature. -5 It can have an ionic conductivity of S / cm or higher. Sulfide-based solid electrolytes are, for example, Li3PO4-Li2SO4, Li2S-P2S5, Li2S-P2S5-LiX, where X is a halogen element, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , m, n are positive numbers, Z is one of Ge, Zn, or Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , p, q are positive numbers, M is one of P, Si, Ge, B, Al, Ga, In, Li 7-x PS 6-x Cl x , 0≤x≤2, Li 7-x PS 6-x Br x , 0≤x≤2, and Li 7-x PS 6-x I xIt may include one or more selected from , 0≤x≤2. The sulfide-based solid electrolyte comprises an argyrodite-type solid electrolyte, and the argyrodite-type solid electrolyte may include one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I. The density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc, and the sulfide-based solid electrolyte is in the form of particles, and the average particle size (D50) of the particles is 0.1 μm to 1.9 μm. The oxide-based solid electrolyte comprises, for example, Li, O, and transition metal elements, and may optionally include other elements. The oxide-based solid electrolyte is, for example, 1×10 at room temperature. -5 The solid electrolyte may have an ionic conductivity of S / cm or higher. The oxide-based solid electrolyte may be selected from among oxide-based solid electrolytes used in the solid electrolyte layer. The solid electrolyte may be, for example, a mixture of a sulfide-based solid electrolyte and a lithium salt. For example, it may be a mixture of Li3PO4-Li2SO4 and a binary lithium salt or a mixture of Li3PO4-Li2SO4 and a ternary lithium salt.
[0097] The complex of Li2S and a solid electrolyte includes a solid electrolyte. The solid electrolyte refers to the complex of Li2S, carbon, and a solid electrolyte described above.
[0098] A complex of Li2S, a lithium salt, and carbon comprises a lithium salt compound and carbon. The lithium salt compound does not contain, for example, sulfur (S) atoms. The lithium salt compound may be a binary compound composed, for example, of lithium and one element selected from Groups 13 to 17 of the periodic table. The binary compound may comprise, for example, one or more selected from LiF, LiCl, LiBr, LiI, LiH, Li2S, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, LiI3, and LiB3. The lithium salt compound may be a ternary compound composed, for example, of lithium and two elements selected from Groups 13 to 17 of the periodic table. The ternary compound comprises, for example, one or more selected from Li3OCl, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiNO3, Li2CO3, LiBH4, Li2SO4, Li3BO3, Li3PO4, Li4NCl, Li5NCl2, and Li3BN2. The lithium salt compound is, in particular, one or more lithium halide compounds selected from LiF, LiCl, LiBr, and LiI. Carbon refers to the complex of Li2S and carbon described above.
[0099] The complex of Li2S and metal carbide contains metal carbide. The metal carbide is, for example, a two-dimensional metal carbide. A two-dimensional metal carbide is, for example, MXene. A two-dimensional metal carbide is, for example, M n+1 C n T x It is expressed as (M is a transition metal, T is a terminal group, T is O, OH and / or F, n=1, 2, or 3, and x is the number of terminal groups). Two-dimensional metal carbides are, for example, Ti2CT x , (Ti 0.5 , Nb 0.5 )2CT x , Nb2CT x , V2CT x, Ti3C2T x , (V 0.5 , Cr 0.5 )3C2T x , Ti3CNT x , Ta4C3T x , Nb4C3T x Or a combination of these. The surface of a two-dimensional metal carbide is terminated by O, OH and / or F.
[0100] The complex of Li2S, carbon, and metal carbide includes carbon and metal carbide. Carbon refers to the complex of Li2S and carbon described above. Metal carbide refers to the complex of Li2S and metal carbide described above.
[0101] The complex of Li2S and metal nitride contains the metal nitride. The metal nitride is, for example, a two-dimensional metal nitride. The two-dimensional metal nitride is, for example, M n+1 N n T x It is expressed as (M is a transition metal, T is a terminal group, T is O, OH and / or F, n=1, 2, or 3, and x is the number of terminal groups). The surface of a two-dimensional metal nitride is terminated by O, OH and / or F.
[0102] The complex of Li2S, carbon, and metal nitride includes carbon and metal nitride. Carbon refers to the complex of Li2S and carbon described above. Metal carbide refers to the complex of Li2S and metal nitride described above.
[0103] The size of the cathode active material may be, for example, 0.1 to 50 μm, 0.5 to 30 μm, 0.5 to 20 μm, or 1 to 10 μm. The size of Li2S may be, for example, 1 nm to 10 μm, 10 nm to 5 μm, 10 nm to 3 μm, or 10 nm to 1 μm. The size of the Li2S-containing composite may be, for example, 0.1 to 50 μm, 0.5 to 30 μm, 0.5 to 20 μm, or 1 to 10 μm.
[0104] The positive active material layer (12) may additionally include a sulfide-based compound that is distinct from the positive active material described above, for example. The sulfide-based compound may be a compound containing, for example, a metal element other than Li and a sulfur element. The sulfide-based compound may be a compound containing, for example, a metal element belonging to Group 1 to Group 14 of the periodic table with an atomic weight of 10 or more and a sulfur element. The sulfide-based compound may be, for example, FeS2, VS2, NaS, MnS, FeS, NiS, CuS, or a combination thereof. By additionally including a sulfide-based compound in the positive active material layer, the cycle characteristics of the solid secondary battery may be further improved. The content of such a sulfide-based compound included in the positive active material layer (12) may be 10 wt% or less, 5 wt% or less, 3 wt% or less, or 1 wt% or less of the total weight of the positive active material layer (12).
[0105] The shape of the positive active material is, for example, a particle shape such as a sphere, an elliptical sphere, etc. The particle size of the positive active material is not particularly limited and is within a range applicable to the positive active material of a conventional solid secondary battery. The content of the positive active material of the positive layer (10) is also not particularly limited and is within a range applicable to the positive layer of a conventional solid secondary battery. The content of the positive active material included in the positive active material layer (12) may be, for example, 30 wt% to 99 wt%, 30 wt% to 90 wt%, 30 wt% to 80 wt%, 30 wt% to 70 wt%, or 30 wt% to 50 wt% of the total weight of the positive active material layer (12).
[0106] [Bipolar: Challenge Material]
[0107] The positive electrode active material layer (12) may further include a conductive material. The conductive material may be, for example, a carbon-based conductive material, a metal-based conductive material, or a combination thereof. The carbon-based conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or a combination thereof, but is not limited to these, and any material used as a carbon-based conductive material in the relevant technical field is possible. The metal-based conductive material may be metal powder, metal fiber, or a combination thereof, but is not limited to these, and any material used as a metal-based conductive material in the relevant technical field is possible. The content of the conductive material included in the positive electrode active material layer (12) may be, for example, 1 wt% to 30 wt%, 1 wt% to 20 wt%, or 1 wt% to 10 wt% of the total weight of the positive electrode active material layer (12).
[0108] [Positive: Binder]
[0109] The positive active material layer (12) may further include a binder. The binder may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited to these and any binder used in the relevant technical field may be used. The binder content included in the positive active material layer (12) may be, for example, 1 wt% to 10 wt% of the total weight of the positive active material layer (12). The binder may be omitted.
[0110] [Anode: Other Additives]
[0111] The positive active material layer (12) may further include additives such as fillers, coating agents, dispersants, and ion conductivity aids in addition to the positive active material, solid electrolyte, binder, and conductive material described above.
[0112] The filler, coating agent, dispersant, ion-conducting auxiliary agent, etc. that the positive electrode active material layer (12) may include can be any known material generally used in the electrodes of solid secondary batteries.
[0113] [Polygonal: Positive current collector]
[0114] The positive current collector (11) is made of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof, such as a plate or foil. The positive current collector (11) may be omitted. The thickness of the positive current collector (11) is, for example, 1 μm to 100 μm, 1 μm to 50 μm, 5 μm to 25 μm, or 10 μm to 20 μm.
[0115] The positive current collector (11) may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The base film may be, for example, an insulator. By including an insulating thermoplastic polymer in the base film, the base film may soften or liquefy upon a short circuit, thereby blocking battery operation and suppressing a sudden increase in current. The metal layer may include indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), or alloys thereof. The metal layer may act as an electrochemical fuse and cut off in the event of an overcurrent to perform a short-circuit prevention function. The limit current and maximum current can be controlled by adjusting the thickness of the metal layer. The metal layer may be plated or deposited on a base film. As the thickness of the metal layer decreases, the limit current and / or maximum current of the positive current collector (11) decreases, thereby improving the stability of the lithium battery in the event of a short circuit. A lead tab may be added to the metal layer for external connection.A lead tab can be welded to a metal layer or a metal layer / base film laminate by means of ultrasonic welding, laser welding, spot welding, etc. During welding, the base film and / or metal layer melt, allowing the metal layer to be electrically connected to the lead tab. To make the weld between the metal layer and the lead tab more robust, a metal chip may be added between the metal layer and the lead tab. The metal chip may be a thin sheet of the same material as the metal in the metal layer. The metal chip may be, for example, metal foil, metal mesh, etc. The metal chip may be, for example, aluminum foil, copper foil, SUS foil, etc. The lead tab may be welded to a metal chip / metal layer laminate or a metal chip / metal layer / base film laminate by placing the metal chip on the metal layer and then welding it to the lead tab. During welding, the base film, metal layer, and / or metal chip melt, allowing the metal layer or the metal layer / metal chip laminate to be electrically connected to the lead tab. A metal chip and / or lead tab may be added to a portion of the metal layer. The thickness of the base film may be, for example, 1 to 50 μm, 1.5 to 50 μm, 1.5 to 40 μm, or 1 to 30 μm. By having the base film within this thickness range, the weight of the electrode assembly can be reduced more effectively. The melting point of the base film may be, for example, 100 to 300 °C, 100 to 250 °C or less, or 100 to 200 °C. By having the base film within this melting point range, the base film can melt during the welding process of the lead tab and be easily bonded to the lead tab. Surface treatments, such as corona treatment, may be performed on the base film to improve the adhesion between the base film and the metal layer. The thickness of the metal layer may be, for example, 0.01 to 3 μm, 0.1 to 3 μm, 0.1 to 2 μm, or 0.1 to μm.By having the metal layer have a thickness within this range, the stability of the electrode assembly can be ensured while maintaining conductivity. The thickness of the metal piece may be, for example, 2 to 10 μm, 2 to 7 μm, or 4 to 6 μm. By having the metal piece have a thickness within this range, the connection between the metal layer and the lead tab can be performed more easily. By having the positive current collector (11) have this structure, the weight of the positive electrode can be reduced, and consequently, the energy density of the positive electrode and the lithium battery can be improved.
[0116] [Polygon: Inert component]
[0117] Referring to FIGS. 4 and 5, the anode (10) comprises an anode current collector (11) and an anode active material layer (12) disposed on one side of the anode current collector. An inactive member (40) is disposed on one side of the anode (10). Referring to FIG. 4, the inactive member (40) is disposed on one side of the anode active material layer (12) and the anode current collector (11). Referring to FIG. 5, the inactive member (40) is disposed on one side of the anode active material layer (12) and is disposed between the solid electrolyte layer (30) and the anode current collector (11) facing the solid electrolyte layer (30). The inactive member (40) is not disposed on one side of the anode current collector (11).
[0118] By including an inert member (40), cracking of the electrolyte layer (30) is prevented during manufacturing and / or charging and discharging of the solid secondary battery (1), and consequently, the cycle characteristics of the solid secondary battery (2) are improved. In a solid secondary battery (1) that does not include an inert member (40), uneven pressure is applied to the electrolyte layer (30) in contact with the positive electrode (10) during manufacturing and / or charging and discharging of the solid secondary battery (1), causing cracking in the electrolyte layer (30), and the likelihood of a short circuit occurring due to the growth of lithium metal through this increases.
[0119] In the solid secondary battery (1), the thickness of the inert member (40) is greater than or equal to the thickness of the positive active material layer (12). Alternatively, in the solid secondary battery (1), the thickness of the inert member (40) is substantially equal to the thickness of the positive electrode (10). Since the thickness of the inert member (40) is equal to the thickness of the positive electrode (10), a uniform pressure is applied between the positive electrode (10) and the electrolyte layer (30), and the positive electrode (10) and the electrolyte layer (30) are sufficiently in contact, thereby reducing the interfacial resistance between the positive electrode (10) and the electrolyte layer (30). Additionally, as the electrolyte layer (30) is sufficiently sintered during the pressurized manufacturing process of the solid secondary battery (1), the internal resistance of the electrolyte layer (30) and the solid secondary battery (1) containing it is reduced.
[0120] The inert member (40) surrounds the side of the anode (10) and comes into contact with the electrolyte layer (30). By the inert member (40) surrounding the side of the anode (10) and coming into contact with the electrolyte layer (30), cracks in the electrolyte layer (30) caused by pressure differences during the pressing process in the electrolyte layer (30) that does not come into contact with the anode (20) can be effectively suppressed. The inert member (40) surrounds the side of the anode (10) and is separated from the cathode (20), more specifically from the first cathode active material layer (22). The inert member (40) surrounds the side of the anode (10), comes into contact with the electrolyte layer (30), and is separated from the cathode (20). Therefore, the possibility of a short circuit occurring due to physical contact between the anode (10) and the first cathode active material layer (22), or due to overcharging of lithium, is suppressed. For example, by placing an inert member (40) on one side of the positive active material layer (12) and simultaneously placing it on one side of the positive current collector (11), the possibility of a short circuit occurring due to contact between the positive current collector (11) and the negative electrode (20) is more effectively suppressed.
[0121] Referring to FIGS. 4 and 5, the inert member (40) extends from one side of the anode (30) to the end portion of the electrolyte layer (30). By extending the inert member (40) to the end portion of the electrolyte layer (30), cracks occurring at the end portion of the electrolyte layer (30) can be suppressed. The end portion of the electrolyte layer (30) is the outermost portion that contacts the side of the electrolyte layer (30). The inert member (40) extends to the outermost portion that contacts the side of the electrolyte layer (30). The inert member (40) is separated from the cathode (20), more specifically from the first cathode active material layer (22). The inert member (40) extends to the end portion of the electrolyte layer (30) but does not come into contact with the cathode (20). The inert member (40) fills the space extending from one side of the anode (30) to the end of the electrolyte layer (30), for example.
[0122] Referring to FIGS. 4 and 5, the width of the inert member (40) extending from one side of the anode (10) to the end portion of the electrolyte layer (30) is, for example, 1 to 30%, 1 to 25%, 1 to 20%, 1 to 15%, 1 to 10%, or 1 to 5% of the width between one side of the anode (10) and the other side facing said one side. If the width of the inert member (40) is excessively large, the energy density of the solid secondary battery (1) is reduced. If the width of the inert member (40) is excessively small, the effect of placing the inert member (40) is negligible.
[0123] The area of the anode (10) is smaller than the area of the electrolyte layer (30) in contact with the anode (10). An inert member (40) is arranged to surround the side of the anode (10) to compensate for the difference in area between the anode (10) and the electrolyte layer (30). By compensating for the difference in area between the anode (10) and the electrolyte layer (30) with the area of the inert member (40), cracks in the electrolyte layer (30) caused by pressure differences during the pressing process are effectively suppressed. For example, the sum of the area of the anode (10) and the area of the inert member (40) is equal to the area of the electrolyte layer (30). The electrolyte layer (30) may be, for example, a solid electrolyte layer.
[0124] The area of the anode (10) is, for example, less than 100%, 99% or less, 98% or less, 97% or less, 96% or less, or 95% or less of the area of the electrolyte layer (30). The area of the anode (10) is, for example, 50% to less than 100%, 50% to 99%, 55% to 98%, 60% to 97%, 70% to 96%, 80% to 95%, or 85% to 95% of the area of the electrolyte layer (30).
[0125] If the area of the positive electrode (10) is equal to or larger than the area of the electrolyte layer (30), the possibility of a short circuit occurring due to physical contact between the positive electrode (10) and the first negative electrode active material layer (22) or due to overcharging of lithium increases. The area of the positive electrode (10) is, for example, equal to the area of the positive electrode active material layer (12). The area of the positive electrode (10) is, for example, equal to the area (11) of the positive electrode current collector.
[0126] The area of the inert member (40) is, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the area of the anode (10). The area of the inert member (40) is, for example, 1% to 50%, 5% to 40%, 5% to 30%, 5% to 20%, or 5% to 15% of the area of the anode (10).
[0127] The area (S1) of the anode (10) is smaller than the area (S4) of the negative electrode current collector (21). The area (S1) of the anode (10) is, for example, less than 100%, 99% or less, 98% or less, 97% or less, 96% or less, or 95% or less of the area (S4) of the negative electrode current collector (21). The area (S1) of the anode (10) is, for example, 50% to less than 100%, 50% to 99%, 55% to 98%, 60% to 97%, 70% to 96%, 80% to 95%, or 85% to 95% of the area (S4) of the negative electrode current collector (21). The area (S4) of the negative electrode current collector (21) is, for example, the same as the area of the negative electrode (20). The area (S4) of the negative electrode current collector (21) is, for example, the same as the area of the first negative electrode active material layer (22).
[0128] In the present disclosure, "identical" area, length, width, thickness, and / or shape includes all cases having "substantially identical" area, length, width, thickness, and / or shape, except where the area, length, width, thickness, and / or shape are intentionally made different from one another. "Identical" area, length, width, and / or thickness includes a range in which the unintended difference in the area, length, width, and / or thickness of the objects being compared is, for example, less than 3%, less than 2%, less than 1%, less than 0.5%, or less than 0.1%.
[0129] The thickness of the inert member (40) is, for example, greater than the thickness of the first cathode active material layer (22). The thickness of the first cathode active material layer (22) is, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the thickness of the inert member (40). The thickness of the first cathode active material layer (22) is, for example, 1% to 50%, 1% to 40%, 1% to 30%, 1% to 20%, or 1% to 10% of the thickness of the inert member (40).
[0130] The inert member (40) may be a gasket. By using a gasket as the inert member (40), cracks in the electrolyte layer (30) caused by pressure differences during the pressurization process can be effectively suppressed.
[0131] The inert member (40) has, for example, a single-layer structure. Alternatively, although not shown in the drawings, the inert member (40) may have a multi-layer structure. In the inert member (40) having a multi-layer structure, each layer may have a different composition. The inert member having a multi-layer structure may have, for example, a two-layer structure, a three-layer structure, a four-layer structure, or a five-layer structure. The inert member (40) having a multi-layer structure may include, for example, one or more adhesive layers and one or more support layers. The adhesive layer effectively prevents separation between the positive electrode (10) and the electrolyte layer (30) caused by volume changes of the positive electrode (10) during the charging and discharging process of the solid secondary battery (10), for example, and improves the film strength of the inert member (40) by providing a bonding force between the support layer and other layers. The support layer provides support to the inert member (40), prevents non-uniformity of pressure applied to the electrolyte layer (30) during the pressurization process or the charging / discharging process, and prevents deformation of the solid secondary battery (1) being manufactured.
[0132] The inert member (40) is, for example, a flame-retardant inert member. By providing flame retardancy, the flame-retardant inert member can prevent thermal runaway and the possibility of ignition of the solid secondary battery (1). As a result, the safety of the solid secondary battery (1) is further improved. By absorbing residual moisture within the solid secondary battery (1), the flame-retardant inert member prevents the deterioration of the solid secondary battery (1), thereby improving the lifespan characteristics of the solid secondary battery (1).
[0133] The flame-retardant inert member includes, for example, a metallic and a filler. The metallic includes, for example, a substrate and a reinforcing material. The metallic includes, for example, a fibrous substrate and a fibrous reinforcing material. By including a substrate, the metallic may have elasticity. Thus, the metallic can effectively accommodate volume changes during the charging and discharging of the solid secondary battery (1) and can be placed at various locations. The substrate included in the metallic includes, for example, a first fibrous material. By including the first fibrous material, the substrate can effectively accommodate volume changes of the positive electrode (30) that occur during the charging and discharging process of the solid secondary battery (1), and can effectively suppress deformation of the inert member (40) caused by volume changes of the positive electrode (30). The first fibrous material is, for example, a material having an aspect ratio of 5 or more, 20 or more, or 50 or more. The first fibrous material is, for example, a material having an aspect ratio of 5 to 1000, 20 to 1000, or 50 to 1000. The first fibrous material is, for example, an insulating material. Since the first fibrous material is an insulating material, it is possible to effectively prevent a short circuit between the positive electrode (30) and the negative electrode (20) caused by lithium dendrites, etc., that occur during the charging and discharging process of the solid secondary battery (1). The first fibrous material includes one or more selected from, for example, pulp fiber, insulating polymer fiber, and ion-conducting polymer fiber. The strength of the metalrix is enhanced by the inclusion of a reinforcing material in the metalrix. Therefore, the metalrix can prevent excessive volume change during the charging and discharging of the solid secondary battery (1) and prevent deformation of the solid secondary battery. The reinforcing material included in the metalrix includes, for example, a second fibrous material. By including the second fibrous material in the reinforcing material, the strength of the metalrix can be increased more uniformly. The second fibrous material is, for example, a material with an aspect ratio of 3 or more, 5 or more, or 10 or more.The first fibrous material is, for example, a material with an aspect ratio of 3 to 100, 5 to 100, or 10 to 100. The second fibrous material is, for example, a flame-retardant material. Since the second fibrous material is a flame-retardant material, ignition caused by thermal runaway occurring during the charging and discharging process of the solid secondary battery (1) or due to external impact can be effectively suppressed. The second fibrous material is, for example, glass fiber, metal oxide fiber, ceramic fiber, etc.
[0134] The flame-retardant inert member includes a filler in addition to the metals. The filler may be placed inside the metals, on the surface of the metals, or on both the inside and the surface. The filler is, for example, an inorganic material. The filler included in the flame-retardant inert member is, for example, a moisture getter. The filler prevents the deterioration of the solid secondary battery (1) by removing residual moisture within the solid secondary battery (1) by adsorbing moisture at, for example, a temperature below 100°C. Additionally, if the temperature of the solid secondary battery (1) increases to 150°C or higher due to thermal runaway caused by the charging and discharging process of the solid secondary battery (1) or external impact, the filler can effectively suppress the ignition of the solid secondary battery (1) by releasing the adsorbed moisture. That is, the filler is, for example, a flame retardant. The filler is, for example, a metal hydroxide having moisture adsorption properties. The metal hydroxide included in the filler is, for example, Mg(OH)2, Fe(OH)3, Sb(OH)3, Sn(OH)4, TI(OH)3, Zr(OH)4, Al(OH)3, or a combination thereof. The content of the filler included in the flame-retardant inert member is, for example, 10 to 80 parts by weight, 20 to 80 parts by weight, 30 to 80 parts by weight, 40 to 80 parts by weight, 50 to 80 parts by weight, 60 to 80 parts by weight, or 65 to 80 parts by weight, based on 100 parts by weight of the flame-retardant inert member (4).
[0135] The flame-retardant inert member may further include, for example, a binder. The binder may include, for example, a curable polymer or a non-curable polymer. A curable polymer is a polymer that is cured by heat and / or pressure. A curable polymer is, for example, a solid at room temperature. The flame-retardant inert member (40) includes, for example, a heat-pressure curable film and / or a cured product thereof. A heat-pressure curable polymer is, for example, Toray's TSA-66.
[0136] The flame-retardant inert material may additionally include other materials in addition to the substrate, reinforcing material, filler, and binder described above. The flame-retardant inert material may further include one or more materials selected from, for example, paper, insulating polymers, ion-conducting polymers, insulating inorganic materials, oxide-based solid electrolytes, and sulfide-based solid electrolytes. The insulating polymer may be an olefin-based polymer, for example, polypropylene (PP) or polyethylene (PE).
[0137] The density of the substrate or the density of the reinforcing material included in the flame-retardant inert member may be, for example, 10% to 300%, 10% to 150%, 10% to 140%, 10% to 130%, or 10% to 120% of the density of the anode active material included in the anode active material layer (12).
[0138] The inert member (40) is a member that does not contain a material having electrochemical activity, such as an electrode active material. The electrode active material is a material that absorbs / releases lithium. The inert member (40) is a member made of a material other than the electrode active material, such as a material used in the relevant technical field.
[0139] [cathode]
[0140] [Cathode: Cathode active material]
[0141] Referring to FIGS. 1 to 5, the cathode (20) includes a cathode current collector (21) and a first cathode active material layer (22) disposed on one side of the cathode current collector (21).
[0142] The first negative electrode active material layer (22) is, for example, a metal layer, and the metal layer may include lithium or a lithium alloy.
[0143] Alternatively, the first negative electrode active material layer (22) may include, for example, a negative electrode active material and a binder.
[0144] The cathode active material included in the first cathode active layer (22) is a cathode material that can form an alloy or compound with, for example, lithium.
[0145] The negative electrode active material included in the first negative electrode active material layer (22) has, for example, a particle shape. The average particle size of the negative electrode active material having a particle shape is, for example, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, 500 nm or less, 300 nm or less, or 100 nm or less. The average particle size of the negative electrode active material having a particle shape is, for example, 10 nm to 4 μm, 10 nm to 3 μm, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 300 nm, or 10 nm to 100 nm. By having the negative electrode active material have an average particle size within this range, reversible absorption and / or desorption of lithium during charging and discharging may be more easily facilitated. The average particle size of the cathode active material is, for example, the median diameter (D50) measured using a laser particle size distribution meter.
[0146] The cathode active material included in the first cathode active material layer (22) comprises, for example, one or more selected from carbon-based cathode active materials and metal or metalloid cathode active materials.
[0147] Carbon-based cathode active materials include, for example, amorphous carbon, crystalline carbon, porous carbon, or a combination thereof.
[0148] The carbon-based cathode active material is, in particular, amorphous carbon. Amorphous carbon is, for example, carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, etc., but is not necessarily limited to these, and any material classified as amorphous carbon in the relevant technical field is acceptable. Amorphous carbon is carbon that does not have crystallinity or has very low crystallinity, and is distinguished from crystalline carbon or graphite-based carbon.
[0149] The carbon-based cathode active material may be, for example, porous carbon. The pore volume contained in the porous carbon is, for example, 0.1 cc / g to 10.0 cc / g, 0.5 cc / g to 5 cc / g, or 0.1 cc / g to 1 cc / g. The average pore diameter contained in the porous carbon is, for example, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 10 nm. The BET specific surface area of the porous carbon is, for example, 100 m² 2 / g to 3000 m 2 / g is.
[0150] The metal or metalloid cathode active material comprises one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn), but is not necessarily limited to these; any metal cathode active material or metalloid cathode active material that forms an alloy or compound with lithium in the relevant technical field is acceptable. For example, nickel (Ni) is not a metal cathode active material because it does not form an alloy with lithium.
[0151] The first negative electrode active material layer (22) may include a type of negative electrode active material among these negative electrode active materials, or may include a mixture of multiple different negative electrode active materials. For example, the first negative electrode active material layer (22) may include only amorphous carbon, or one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the first negative electrode active material layer (22) may include a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixing ratio of a mixture of amorphous carbon and gold, etc., is, for example, 99:1 to 1:99, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1 by weight ratio, but is not necessarily limited to these ranges and is selected according to the required characteristics of the solid secondary battery (1). By having the negative electrode active material have this composition, the cycle characteristics of the solid secondary battery (1) are further improved.
[0152] The negative electrode active material included in the first negative electrode active material layer (22) comprises a mixture of first particles made of, for example, amorphous carbon and second particles made of a metal or metalloid. The metal or metalloid includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the metalloid is a semiconductor. The content of the second particles is 1 to 99 weight%, 1 to 60 weight%, 8 to 60 weight%, 10 to 50 weight%, 15 to 40 weight%, or 20 to 30 weight% based on the total weight of the mixture. By having the second particles in this range, the cycle characteristics of, for example, the solid secondary battery (1) are further improved.
[0153] Alternatively, the first negative electrode active material layer (22) comprises a composite negative electrode active material. The composite negative electrode active material may include, for example, a carbon-based support and a metal-based negative electrode active material supported on the carbon-based support. By having such a structure, localization of the metal-based negative electrode active material within the first negative electrode active material layer is prevented, and a uniform distribution can be obtained. Consequently, the cycle characteristics of the solid secondary battery (1) comprising the first negative electrode active material layer (22) are further improved.
[0154] A metal-based cathode active material supported on a carbon-based support comprises, for example, a metal, a metal oxide, a composite of a metal and a metal oxide, or a combination thereof. The metal includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), tellurium (Te), and zinc (Zn). The metal oxide includes, for example, gold (Au) oxide, platinum (Pt) oxide, palladium (Pd) oxide, silicon (Si) oxide, silver (Ag) oxide, aluminum (Al) oxide, bismuth (Bi) oxide, tin (Sn) oxide, tellurium (Te) oxide, and zinc (Zn) oxide. Metal oxides are, for example, Au x O y (0 <x≤2, 0<y≤3), Pt x O y (0 <x≤1, 0<y≤2), Pd x O y (0 <x≤1, 0<y≤1), Si x O y (0 <x≤1, 0<y≤2), Ag x O y (0 <x≤2, 0<y≤1), Al x O y (0 <x≤2, 0<y≤3), Bi x O y (0 <x≤2, 0<y≤3), Sn x O y (0 <x≤1, 0<y≤2), Te x O y (0 <x≤1, 0<y≤3), Zn x O y (0 <x≤1, 0<y≤1) 또는 이들의 조합을 포함할 수 있다. 금속과 금속산화물의 복합체는 예를 들어 Au와 Au x O y (0 <x≤2, 0<y≤3)의 복합체, Pt와 Pt x O y (0 <x≤1, 0<y≤2)의 복합체, Pd와 Pd x O y (0 <x≤1, 0<y≤1)의 복합체, Si와 Si x O y (0 <x≤1, 0<y≤2)의 복합체, Ag 와 Ag x O y (0 <x≤1, 0<y≤2)의 복합체, Al과 Al x O y (0 <x≤2, 0<y≤3)의 복합체, Bi와 Bi x O y (0 <x≤2, 0<y≤3)의 복합체, Sn과 Sn x O y (0 <x≤1, 0<y≤2)의 복합체, Te과 Te x O y(0 <x≤1, 0<y≤3), Zn과 Zn x O y (0 <x≤1, 0<y≤1)의 복합체, 또는 이들의 조합을 포함할 수 있다.
[0155] The carbon-based support is, for example, amorphous carbon. Amorphous carbon includes, for example, carbon black (CB), acetylene black (AB), furnace black (FB), Kettjen black (KB), graphene, activated carbon, carbon nanofibers (CNF), carbon nanotubes (CNT), etc., but is not necessarily limited to these; any material classified as amorphous carbon in the relevant technical field is acceptable. Amorphous carbon is carbon that does not possess crystallinity or has very low crystallinity, and is distinguished from crystalline carbon or graphite-based carbon. The carbonaceous material is, for example, a carbon-based negative electrode active material.
[0156] The composite cathode active material has, for example, a particle form. The particle size of the composite cathode active material having a particle form is, for example, 10 nm to 4 µm, 10 nm to 1 µm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. Since the composite cathode active material has a particle size within this range, the reversible absorption and / or desorption of lithium during charging and discharging may be more facilitated. The metal-based cathode active material supported on the support may have, for example, a particle form. The particle size of the metal-based cathode active material may be, for example, 1 nm to 200 nm, 1 nm to 150 nm, 5 nm to 100 nm, or 10 nm to 50 nm. The carbon-based support may have, for example, a particle form. The particle size of the carbon-based support may be, for example, 10 nm to 2 µm, 10 nm to 1 µm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. By having a particle size within this range, the carbon-based support can be distributed more uniformly within the first negative electrode active material layer. The carbon-based support may be, for example, nanoparticles with a particle size of 500 nm or less. The particle size of the composite negative electrode active material, the particle size of the metal-based negative electrode active material, and the particle size of the carbon-based support are, for example, average particle sizes. The average particle size is, for example, the median diameter (D50) measured using a laser particle size distribution meter. Alternatively, the average particle size may be determined automatically using software from, for example, electron microscope images, or manually by manual.
[0157] [Cathode: Binder]
[0158] The binder included in the first negative electrode active material layer (22) may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited to these and any binder used in the relevant technical field is possible. The binder may be composed of a single binder or a plurality of different binders.
[0159] The first negative active material layer (22) is stabilized on the negative current collector (21) by including a binder. Additionally, cracking of the first negative active material layer (22) is suppressed despite changes in volume and / or relative position of the first negative active material layer (22) during the charging and discharging process. For example, if the first negative active material layer (22) does not include a binder, it is possible for the first negative active material layer (22) to be easily separated from the negative current collector (21). As the first negative active material layer (22) is separated from the negative current collector (21), the possibility of a short circuit occurring increases in the portion of the negative current collector (21) that is exposed due to the first negative active material layer (22) coming into contact with the electrolyte layer (30). The first negative electrode active material layer (22) is manufactured by, for example, applying a slurry in which the material constituting the first negative electrode active material layer (22) is dispersed onto a negative electrode current collector (21) and drying it. By including a binder in the first negative electrode active material layer (22), stable dispersion of the negative electrode active material in the slurry is possible. For example, when applying the slurry onto the negative electrode current collector (21) using a screen printing method, it is possible to suppress clogging of the screen (for example, clogging caused by aggregates of the negative electrode active material).
[0160] [Cathode: Other Additives]
[0161] The first negative electrode active material layer (22) may further include additives used in conventional solid secondary batteries (1), such as fillers, coating agents, dispersants, ion-conducting aids, etc.
[0162] [Cathode: Solid Electrolyte]
[0163] The first negative electrode active material layer (22) may further include a solid electrolyte. The solid electrolyte may be a material selected from, for example, the solid electrolyte included in the electrolyte layer (30). The solid electrolyte included in the first negative electrode active material layer (22) may act as a reaction site where the formation of lithium metal begins within the first negative electrode active material layer (22), act as a space where the formed lithium metal is stored, or act as a path for transmitting lithium ions. The solid electrolyte may be omitted.
[0164] In the first negative electrode active material layer (22), the content of the solid electrolyte may be high in the region adjacent to the electrolyte layer (30), for example, and low in the region adjacent to the negative electrode current collector (21). In the first negative electrode active material layer (22), the solid electrolyte may have a concentration gradient in which the concentration decreases from, for example, the region adjacent to the electrolyte layer (30) to the region adjacent to the negative electrode current collector (21).
[0165] [Cathode: First cathode active material layer]
[0166] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer (22) and the initial charge capacity (A) of the positive electrode active material layer is 0.005 to 0.45. The initial charge capacity of the positive electrode active material layer (12) is the first open circuit voltage (1 st From open circuit voltage) Li / Li + The initial charging capacity of the first negative electrode active material layer (22) is determined at the maximum charging voltage. nd From open circuit voltage) Li / Li + It is determined at 0.01 V for.
[0167] The maximum charging voltage is determined according to the type of cathode active material. The maximum charging voltage can be, for example, 1.5 V, 2.0 V, 2.5 V, 3.0 V, 3.5 V, 4.0 V, 4.2 V, or 4.3 V. For example, the maximum charging voltage of Li2S or a Li2S-containing composite is Li / Li + It can be 2.5 V. For example, the maximum charging voltage of Li2S or a Li2S-containing composite is Li / Li + The V may be 3.0 V. The ratio (B / A) of the initial charge capacity (B) of the first negative active material layer (22) and the initial charge capacity (A) of the positive active material layer is, for example, 0.01 to 0.3, 0.01 to 0.2, or 0.05 to 0.1. The initial charge capacity (mAh) of the positive active material layer (12) is obtained by multiplying the charge specific capacity (mAh / g) of the positive active material by the mass (g) of the positive active material in the positive active material layer (12). When multiple types of positive active materials are used, the charge specific capacity × mass value is calculated for each positive active material, and the sum of these values is the initial charge capacity of the positive active material layer (12). The initial charge capacity of the first negative active material layer (22) is also calculated in the same way. The initial charge capacity of the first negative electrode active material layer (22) is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer (22). If multiple types of negative electrode active materials are used, the charge capacity density × mass value is calculated for each negative electrode active material, and the sum of these values is the initial charge capacity of the first negative electrode active material layer (22). The charge capacity densities of the positive electrode active material and the negative electrode active material, respectively, can be measured using a solid half-cell with lithium metal as the counter electrode. The initial charge capacities of the positive electrode active material layer (12) and the first negative electrode active material layer (22), respectively, are at a constant current density, for example, 0.1 mA / cm² 2This can be directly measured using a solid half-cell. For the anode, the measurement is taken from the first open-circuit voltage (OCV) to the maximum charging voltage, e.g., 3.0 V (vs. Li / Li). + It can be performed for an operating voltage up to ). For the cathode, the measurement can be performed for an operating voltage from the second open circuit voltage (OCV) down to 0.01 V for the cathode, e.g., lithium metal. For example, a solid half-cell having an anode active material layer 0.1 mA / cm² from the first open circuit voltage up to 3.0 V. 2 A solid half-electrode having a first negative electrode active material layer, charged with a constant current, has a voltage of 0.1 mA / cm² up to 0.01 V from the second open circuit voltage. 2 It can be charged with a constant current. The current density during constant current charging is, for example, 0.2 mA / cm² 2 , or 0.5 mA / cm 2 A solid half battery having a positive active material layer can be charged, for example, from a first open-circuit voltage to 2.5 V, 2.0 V, 3.5 V, or 4.0 V. The maximum charging voltage of the positive active material layer can be determined by the maximum voltage of the battery satisfying safety conditions according to JISC8712:2015 of the Japanese Standards Association.
[0168] If the initial charge capacity of the first negative electrode active material layer (22) is excessively small, the thickness of the first negative electrode active material layer (22) becomes very thin, and thus, during repeated charge and discharge processes, lithium dendrites formed between the first negative electrode active material layer (22) and the negative electrode current collector (21) cause the first negative electrode active material layer (22) to collapse, making it difficult to improve the cycle characteristics of the solid secondary battery (1). If the charge capacity of the first negative electrode active material layer (22) increases excessively, the energy density of the solid secondary battery (1) decreases, and the internal resistance of the solid secondary battery (1) caused by the first negative electrode active material layer (22) increases, making it difficult to improve the cycle characteristics of the solid secondary battery (1).
[0169] The thickness of the first negative electrode active material layer (22) is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer (12). The thickness of the first negative electrode active material layer (22) is, for example, 1 to 50%, 1 to 40%, 1 to 30%, 1 to 20%, 1 to 10%, or 1 to 5% of the thickness of the positive electrode active material layer (12). The thickness of the first negative electrode active material layer (22) is, for example, 1 μm to 20 μm, 2 μm to 15 μm, or 3 μm to 10 μm. If the thickness of the first negative electrode active material layer (22) is excessively thin, lithium dendrites formed between the first negative electrode active material layer (22) and the negative electrode current collector (21) cause the first negative electrode active material layer (22) to collapse, making it difficult to improve the cycle characteristics of the solid secondary battery (1). If the thickness of the first negative electrode active material layer (22) is excessively increased, the energy density of the solid secondary battery (1) decreases, and the internal resistance of the solid secondary battery (1) caused by the first negative electrode active material layer (22) increases, making it difficult to improve the cycle characteristics of the solid secondary battery (1). If the thickness of the first negative electrode active material layer (22) decreases, for example, the initial charge capacity of the first negative electrode active material layer (22) also decreases.
[0170] [Cathode: Second cathode active material layer]
[0171] Referring to FIG. 3, the solid secondary battery (1) further comprises a second negative active material layer (24) disposed between, for example, a negative current collector (21) and a first negative active material layer (22) after being charged. The second negative active material layer (24) is a metal layer comprising lithium or a lithium alloy. The metal layer comprises lithium or a lithium alloy. Therefore, since the second negative active material layer (24) is a metal layer comprising lithium, it acts as, for example, a lithium reservoir. The lithium alloy is, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, a Li-Si alloy, etc., but is not limited to these, and any alloy used as a lithium alloy in the relevant technical field is possible. The second negative active material layer (24) may be composed of one of these alloys or lithium, or may be composed of various types of alloys. The second negative electrode active material layer (24) is, for example, a plated layer. The second negative electrode active material layer (24) is, for example, deposited between the first negative electrode active material layer (22) and the negative electrode current collector (21) during the charging process of the solid secondary battery (1).
[0172] The thickness of the second negative electrode active material layer (24) is not particularly limited, but, for example, 1 μm to 500 μm, 1 μm to 200 μm, 1 μm to 150 μm, 1 μm to 100 μm, or 1 μm to 50 μm. If the thickness of the second negative electrode active material layer (24) is excessively thin, it is difficult for the second negative electrode active material layer (24) to perform the role of a lithium reservoir. If the thickness of the second negative electrode active material layer (24) is excessively thick, the mass and volume of the solid secondary battery (1) increase, and there is a possibility that the cycle characteristics of the solid secondary battery (1) may deteriorate.
[0173] Alternatively, in the solid secondary battery (1), the second negative active material layer (24) may be placed between the negative current collector (21) and the first negative active material layer (22) before assembly of the solid secondary battery (1), for example. When the second negative active material layer (24) is placed between the negative current collector (21) and the first negative active material layer (22) before assembly of the solid secondary battery (1), the second negative active material layer (24) acts as a lithium reservoir because it is a metal layer containing lithium. For example, a lithium foil may be placed between the negative current collector (21) and the first negative active material layer (22) before assembly of the solid secondary battery (1).
[0174] When the second negative electrode active material layer (24) is precipitated by charging after assembly of the solid secondary battery (1), the energy density of the solid secondary battery (1) increases because the second negative electrode active material layer (24) is not included during assembly of the solid secondary battery (1). When charging the solid secondary battery (1), it is charged in excess of the charging capacity of the first negative electrode active material layer (22). That is, the first negative electrode active material layer (22) is overcharged. At the beginning of charging, lithium is absorbed in the first negative electrode active material layer (22). The negative electrode active material contained in the first negative electrode active material layer (22) forms an alloy or compound with lithium ions that have moved from the positive electrode (10). When charging is performed beyond the capacity of the first negative electrode active material layer (22), lithium is deposited, for example, on the back surface of the first negative electrode active material layer (22), that is, between the negative current collector (21) and the first negative electrode active material layer (22), and a metal layer corresponding to the second negative electrode active material layer (24) is formed by the deposited lithium. The second negative electrode active material layer (24) is a metal layer composed mainly of lithium (i.e., metallic lithium). This result is obtained, for example, by the negative electrode active material included in the first negative electrode active material layer (22) including a material that forms an alloy or compound with lithium. During discharge, the lithium in the first negative electrode active material layer (22) and the second negative electrode active material layer (24), i.e., the metal layer, is ionized and moves toward the positive electrode (10). Therefore, it is possible to use lithium as a negative electrode active material in a solid secondary battery (1). In addition, since the first negative electrode active material layer (22) covers the second negative electrode active material layer (24), it serves as a protective layer for the second negative electrode active material layer (24), i.e., the metal layer, and at the same time, it performs the role of suppressing the precipitation growth of lithium dendrites. Therefore, it suppresses short circuits and capacity degradation of the solid secondary battery (1), and consequently improves the cycle characteristics of the solid secondary battery (1).Additionally, when the second negative electrode active material layer (24) is formed by charging after assembly of the solid secondary battery (1), the negative electrode (20), that is, the negative electrode current collector (21), the first negative electrode active material layer (22), and the region between them are Li-free regions that do not contain lithium (Li) in the initial state or after complete discharge of the solid secondary battery (1).
[0175] [Cathode: Cathode current collector]
[0176] The negative electrode current collector (21) is composed of a material that does not react with, for example, lithium, that is, does not form any alloys or compounds. The material constituting the negative electrode current collector (21) may be, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni), but is not necessarily limited to these; any material used as an electrode current collector in the relevant technical field is acceptable. The negative electrode current collector (21) may be composed of one of the metals described above, or may be composed of an alloy or coating material of two or more metals. The negative electrode current collector (21) is, for example, in the form of a plate or foil.
[0177] Referring to FIG. 2, the solid secondary battery (1) may further include a thin film (23) containing an element capable of forming an alloy with lithium on one side of the negative electrode current collector (21). The thin film (23) is disposed between the negative electrode current collector (21) and the first negative electrode active material layer (22). The thin film (23) contains, for example, an element capable of forming an alloy with lithium. The element capable of forming an alloy with lithium is, for example, gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, etc., but is not necessarily limited to these, and any element capable of forming an alloy with lithium in the relevant technical field is possible. The thin film (23) is composed of one of these metals or is composed of an alloy of various types of metals. By placing the thin film (23) on one side of the negative electrode current collector (21), the deposition shape of the second negative electrode active material layer (24) deposited between, for example, the thin film (23) and the first negative electrode active material layer (22) is further flattened, and the cycle characteristics of the solid secondary battery (1) can be further improved.
[0178] The thickness of the thin film (23) is, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 nm to 600 nm, or 100 nm to 500 nm. If the thickness of the thin film (23) is less than 1 nm, it may be difficult to perform the function of the thin film (23). If the thickness of the thin film (23) is excessively thick, the thin film (23) itself absorbs lithium, and the amount of lithium precipitated at the negative electrode decreases, which lowers the energy density of the solid battery and may lower the cycle characteristics of the solid secondary battery (1). The thin film (23) may be placed on the negative electrode current collector (21) by, for example, vacuum deposition, sputtering, plating, etc., but is not necessarily limited to these methods, and any method capable of forming the thin film (23) in the relevant technical field is possible.
[0179] Although not shown in the drawing, the negative current collector (21) may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. By including an insulating thermoplastic polymer in the base film, the base film may soften or liquefy upon the occurrence of a short circuit, thereby blocking battery operation and suppressing a sudden increase in current. The metal layer may include indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative electrode current collector (21) may additionally include a metal chip and / or a lead tab. For more specific details regarding the base film, metal layer, metal chip, and lead tab of the negative electrode current collector (21), refer to the positive electrode current collector (11) described above. By having such a structure, the negative electrode current collector (21) can reduce the weight of the negative electrode and, consequently, improve the energy density of the negative electrode and the lithium battery.
[0180] [Solid Electrolyte Layer]
[0181] [Solid Electrolyte Layer: Electrolyte]
[0182] Referring to FIGS. 1 to 5, the solid electrolyte layer (30) is disposed between the anode (10) and the cathode (20) and includes a solid electrolyte separator. The solid electrolyte layer (30) may further include, for example, a solid electrolyte, a gel electrolyte, or a combination thereof.
[0183] The solid electrolyte additionally included in the solid electrolyte layer (30) may include, for example, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof.
[0184] Oxide-based solid electrolytes are, for example, Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2, 0≤y<3), BaTiO3, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0≤x<1, 0≤y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2, 0<y<3), Li x Al y Ti z (PO4)3(0 <x<2, 0<y<1, 0<z<3), Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0≤x≤1 0≤y≤1), Li x La y TiO3(0 <x<2, 0<y<3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Li 3+x La3M2O 12 (M = Te, Nb, or Zr, 0≤x≤10), or a combination thereof. Oxide-based solid electrolytes are produced, for example, by sintering.
[0185] Oxide-based solid electrolytes are, for example, Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O 12 (M-doped LLZO, M=Ga, W, Nb, Ta, or Al, 0 <a<2, 0≤x≤10) 중에서 선택된 가넷계(Garnet-type) 고체전해질이다.
[0186] The polymer solid electrolyte may, for example, comprise a mixture of a lithium salt and a polymer, or comprise a polymer having ion-conducting functional groups. The polymer solid electrolyte may, for example, be a polymer electrolyte that is in a solid state at 25°C and 1 atm. The polymer solid electrolyte may, for example, not contain a liquid.The polymeric solid electrolyte comprises a polymer, wherein the polymer is, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF), poly(methylmethacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylenedioxythiophene (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), Polyaniline, Polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, Sulfonated poly(ether ether ketone) (SPEEK), Sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), Sulfonated poly(aryl ether ketone) (SPAEK), Poly[bis(benzimidazobenzisoquinolinones)] (SPBIBI), Poly(styrene sulfonate) (PSS), Lithium 9,10-Diphenylanthracene-2-sulfonate (lithium 9,10-diphenylanthracene-2-sulfonate, DPASLi. +It may be ) or a combination thereof, but is not limited thereto, and any that are used in polymer electrolytes in the relevant technical field are permitted. Any lithium salt that can be used as a lithium salt in the relevant technical field is permitted. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 The polymer may be SO2)(x and y are each 1 to 20), LiCl, LiI, or a mixture thereof. The polymer included in the polymer solid electrolyte may be, for example, a compound containing 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight-average molecular weight of the polymer included in the polymer solid electrolyte may be, for example, 1,000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.
[0187] Gel electrolytes are, for example, polymeric gel electrolytes. Gel electrolytes can have a gel state without, for example, containing polymers.
[0188] Polymer gel electrolytes may, for example, comprise a liquid electrolyte and a polymer, or comprise an organic solvent and a polymer having ion-conducting functional groups. Polymer gel electrolytes are, for example, 25 It may be a polymer electrolyte in a gel state at 1 atm. The polymer gel electrolyte may, for example, have a gel state without containing liquid. The liquid electrolyte used in the polymer gel electrolyte may be, for example, an ionic liquid, a mixture of a lithium salt and an organic solvent; a mixture of a lithium salt and an organic solvent; a mixture of an ionic liquid and an organic solvent; or a mixture of a lithium salt, an ionic liquid, and an organic solvent. The polymer used in the polymer gel electrolyte may be selected from the polymers used in solid polymer electrolytes. The organic solvent may be selected from the organic solvents used in liquid electrolytes. The lithium salt may be selected from the lithium salts used in solid polymer electrolytes. An ionic liquid refers to a salt or a room-temperature molten salt that has a melting point below room temperature, consists only of ions, and is in a liquid state at room temperature. The ionic liquid may include, for example, a) one or more cations selected from ammonium-based, pyrrolidinium-based, pyridinium-based, pyrimidinium-based, imidazolium-based, piperidinium-based, pyrazolium-based, oxazolium-based, pyridazinium-based, phosphonium-based, sulfonium-based, triazolium-based, and mixtures thereof, and b) one or more compounds selected from BF4-, PF6-, AsF6-, SbF6-, AlCl4-, HSO4-, ClO4-, CH3SO3-, CF3CO2-, Cl-, Br-, I-, SO4-, CF3SO3-, (FSO2)2N-, (C2F5SO2)2N-, (C2F5SO2)(CF3SO2)N-, and (CF3SO2)2N-. A polymer solid electrolyte can form a polymer gel electrolyte by impregnating it into a liquid electrolyte, for example, in a secondary battery. The polymer gel electrolyte may further include inorganic particles. The polymer included in the polymer gel electrolyte may be a compound containing, for example, 10 or more, 20 or more, 50 or more, or 100 or more repeating units.The weight-average molecular weight of the polymer included in the polymer gel electrolyte may be, for example, 500 Dalton or more, 1000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.
[0189] [Anode Manufacturing Method]
[0190] A method for manufacturing an anode according to one embodiment comprises the steps of: providing an adhesive binder layer on an anode current collector; providing a Li2S-containing composite; providing a sulfide-based solid electrolyte; preparing a mixture by mixing the Li2S-containing composite and the sulfide-based solid electrolyte; and preparing to manufacture an anode by adding an adhesive binder to the mixture, mixing the mixture, and providing it on top of the adhesive binder layer to form an anode active material layer.
[0191] A composite of Li2S and a lithium salt can be prepared, for example, by mechanically milling Li2S and a lithium salt. The milling conditions are not particularly limited and any conditions capable of forming the composite are possible. A composite of Li2S and a lithium salt can be prepared by feeding Li2S particles and a lithium salt into a ball mill and stirring at a speed of 100 to 1000 rpm for 1 to 20 hours. Stirring may be performed one or more times.
[0192] As a lithium salt, for example, LiI, LiBr, LiCl, LiF, LiH, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, Li3Al2, LiB3, Li3OCl, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiNO3, Li2CO3, LiBH4, Li2SO4, Li3BO3, Li3PO4, Li4NCl, Li5NCl2, Li3BN2, or a combination thereof may be used.
[0193] A composite of Li2S, a lithium salt, and a carbon-based material can be manufactured, for example, by mechanically milling Li2S and a lithium salt; and adding a carbon-based material to the milled product and milling it.
[0194] A sulfide-based solid electrolyte is provided. The sulfide-based solid electrolyte refers to the solid electrolyte separator portion described above.
[0195] A mixture is prepared by mixing the Li2S-containing composite and the sulfide-based solid electrolyte. The mixing ratio of the Li2S-containing composite and the sulfide-based solid electrolyte may be, for example, a weight ratio of 50:50 to 95:5, 50:50 to 90:10, 50:50 to 80:20, or 50:50 to 70:30.
[0196] The mixture may additionally contain a process solvent. By additionally containing a process solvent, the mixture may have a slurry form. The solvent may be, for example, octyl acetate, but is not limited thereto, and any solvent used in the art is acceptable. Alternatively, the mixture may be prepared dry without containing a process solvent.
[0197] Prepare a solid electrolyte.
[0198] The above adhesive binder layer is formed using a composition for forming an adhesive binder layer containing an adhesive binder.
[0199] As an example of the above adhesive binder, polydopamine is used to explain the method for forming an adhesive binder layer as follows.
[0200] According to one embodiment, a composition for forming a polydopamine layer containing dopamine, a solvent, and a buffer solution is prepared.
[0201] The above dopamine becomes polydopamine through a self-polymerization reaction in a pH range of about 8 to 8.8, for example, about 8.5.
[0202] The pH of the above polydopamine layer-forming composition is 8.0 to 8.8, for example, about 8.5.
[0203] The buffer solution is a solution with a pH of about 8 to 8.8, and examples include a buffer solution containing Tris-HCl and water (the volume ratio of H2O to H2O is 3:1), Tris borate ethylenediamine tetraacetic acid (TBE), Tris-buffered saline (TBS), and phosphate-buffered saline (PBS).
[0204] delete
[0205] As the above solvent, an alcohol-based compound is used as a substance that does not affect the pH of the composition. Examples of alcohol-based compounds include ethanol, methanol, butanol, isopropanol, etc. The content of the solvent is, for example, in the range of 100 to 3,000 parts by weight based on 100 parts by weight of dopamine.
[0206] The above drying is carried out, for example, in a range of 20 to 25°C.
[0207] Examples of the above coatings include dipping, spray coating, bar coating, die casting, comma coating, screen printing, etc. In addition, it is also possible to form an adhesive binder layer on a separate substrate and then bond it to the anode by pressing or lamination. The coating according to one embodiment refers to the spray coating method.
[0208] According to another embodiment, a dopamine monomer, which is a polydopamine precursor, is dissolved in an acid such as HCl to prepare a composition containing an adhesive binder. An anode current collector is immersed in the composition. Subsequently, the resulting product coated with the composition is washed and dried to form an adhesive binder layer.
[0209] According to another embodiment, a polydopamine coating layer composition is prepared in which polydopamine is dispersed in a distilled water buffer solution. This is coated onto the positive current collector and dried to form a polydopamine coating layer, thereby placing an intermediate layer on the surface of the positive current collector. Examples of the coating method include dipping, spray coating, bar coating, die casting, comma coating, screen printing, etc.
[0210] The above drying is carried out at, for example, 30 to 90°C, for example, 80°C.
[0211] The creative idea is explained in more detail through the following examples and comparative examples. However, the examples are intended to illustrate the creative idea and do not limit the scope of the creative idea to these examples alone.
[0212] (Preparation of Li2S and lithium salt composites)
[0213] Preparation Example 1: Li2S-LiI composite
[0214] Li2S and LiI were mixed in a weight ratio of 30:20. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours.
[0215] The size of the Li2S-LiI composite was less than 1 μm. The size of the Li2S-LiI composite was calculated by software from scanning electron microscope images of the Li2S-LiI composite powder. The size of the Li2S-LiI composite is the D50 average particle size.
[0216] The Mohs hardness of Li2S was 0.6, and the Mohs hardness of LiI was 2.0. The Mohs hardness of the Li2S-LiI composite was less than 2.
[0217] Preparation Example 2: Li2S-LiBr complex
[0218] A Li2S-LiBr complex was prepared using the same method as in Preparation Example 1, except that LiBr was used instead of LiI.
[0219] Preparation Example 3: Li2S-LiCl complex
[0220] A Li2S-LiCl complex was prepared using the same method as in Preparation Example 1, except that LiCl was used instead of LiI.
[0221] Comparative Preparation Example 1: Li2S and LiI- simple mixture
[0222] A mixture of Li2S and LiI in a weight ratio of 30:20 was used as is.
[0224] (Preparation of Li2S-LiI-CNF cathode active material)
[0225] Preparation Example 4: Li2S-LiI-CNF(50:30:20), 2 stages, 10 hr, 600 rpm, 28G
[0226] (Stage 1)
[0227] Li2S and LiI were mixed in a weight ratio of 50:30. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 28 G.
[0228] (Stage 2)
[0229] A Li2S-LiI composite and carbon nanofiber (CNF) were mixed in a weight ratio of 80:20. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI-CNF composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 28 G. The Li2S-LiI-CNF composite was used as a composite cathode active material.
[0230] Preparation Example 5: Li2S-LiI-CNF, 2 steps, 8 hr, 600 rpm, 28G
[0231] A Li2S-LiI-CNF composite was prepared using the same method as in Preparation Example 4, except that the milling time in the first and second steps was changed to 8 hours.
[0232] Preparation Example 6: Li 2 S-LiI-CNF, 2 stages, 6 hr, 600 rpm, 28G
[0233] A Li2S-LiI-CNF composite was prepared using the same method as in Preparation Example 4, except that the milling time in the first and second steps was changed to 6 hours.
[0234] Preparation Example 7: Li2S-LiI-CNF, 2 steps, 4 hr, 600 rpm, 28G
[0235] A Li2S-LiI-CNF composite was prepared using the same method as in Preparation Example 4, except that the milling time in the first and second steps was changed to 4 hours.
[0236] Comparative Preparation Example 2: Simple mixture of Li2S, LiI, and CNF
[0237] A mixture of Li2S, LiI, and CNF in a weight ratio of 50:30:20 was used as is.
[0238] Comparative Manufacturing Example 3: Li2S-LiI-CNF, 2 steps, 1 hr, 600 rpm, 28G
[0239] A Li2S-LiI-CNF composite was prepared using the same method as in Preparation Example 4, except that the milling time in the first and second steps was changed to 1 hour.
[0240] Comparative Manufacturing Example 4: Li2S-LiI-CNF, 2 steps, 20 hr, 600 rpm, 28G
[0241] A Li2S-LiI-CNF composite was prepared using the same method as in Preparation Example 4, except that the milling time in the first and second steps was changed to 20 hours.
[0242] Comparative Manufacturing Example 5: Li2S-LiI-CNF, 510 rpm, 10 hr, 2 stages, 20G (KR 2017-0068448 (Tatsumisago), (Stage 1)
[0243] A first mixture was prepared by mixing Li2S and LiI in a weight ratio of 30:20. A Li2S-LiI composite was prepared by mechanically milling the first mixture using a ball mill.
[0244] The milling conditions were 25℃ and 510 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G.
[0245] (Stage 2)
[0246] A second mixture was prepared by mixing a Li2S-LiI composite and carbon nanofiber (CNF) in a weight ratio of 50:10. The second mixture was mechanically milled using a ball mill to produce a Li2S-LiI-CNF composite.
[0247] The milling conditions were 25 ℃ and 510 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G. A Li2S-LiI-CNF composite was used as the composite cathode active material.
[0248] Comparative Manufacturing Example 6: Li2S-LiI-CNF, 10 hr, 2 steps, 10 G
[0249] A Li2S-LiI-CNF composite was prepared in the same manner as in Preparation Example 4, except that the rotational speed was reduced in the first and second steps and the milling energy was changed to 10 G.
[0250] Comparative Manufacturing Example 7: Li2S-LiI-CNF, 10 hr, 2 steps, 30 G
[0251] A Li2S-LiI-CNF composite was prepared in the same manner as in Preparation Example 4, except that the milling energy was changed to 30 G by increasing the rotational speed in the first and second steps.
[0252] Comparative Preparation Example 8: Simple mixture of Li2S and CNF
[0253] Li2S and carbon nanofiber (CNF) were mixed in a weight ratio of 30:30. The mixture was used as is as an anode active material.
[0254] Comparative Manufacturing Example 9: Li2S-CNF, 600 rpm, 2 hr, 1 stage, 20 G
[0255] Li2S and carbon nanofibers (CNF) were mixed in a weight ratio of 30:30. The mixture was mechanically milled using a ball mill to prepare a Li2S-CNF composite. The milling conditions were 25 ℃ and 600 rpm for 2 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-CNF composite was used as a composite cathode active material.
[0256] Comparative Manufacturing Example 10: Li2S-CNF, 600 rpm, 10 hr, 1 stage, 20 G
[0257] A Li2S-CNF composite was prepared using the same method as Comparative Example 7, except that the milling time was changed to 10 hours.
[0258] Comparative Example 11: Li2S-CNF-LiI, 600 rpm, 10 hr, 2 stages, 20G
[0259] (Stage 1)
[0260] Li2S and carbon nanofibers (CNF) were mixed in a weight ratio of 30:10. The mixture was mechanically milled using a ball mill to prepare a Li2S-CNF composite. The milling conditions were 25°C and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G.
[0261] (Stage 2)
[0262] Li2S-CNF composite and LiI were mixed in a weight ratio of 40:20. The mixture was mechanically milled using a ball mill to prepare a Li2S-CNF-LiI composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-CNF-LiI composite was used as a composite cathode active material.
[0263] Comparative Example 12: Li2S-SE-CNF, 600 rpm, 10 hr, 2 stages, 20G
[0264] (Stage 1)
[0265] Li2S and Li6PS5Cl solid electrolyte (SE) were mixed in a weight ratio of 30:20. The mixture was mechanically milled using a ball mill to prepare a Li2S-SE composite. The milling conditions were 25°C and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G.
[0266] (Stage 2)
[0267] The Li2S-SE composite and CNF were mixed in a weight ratio of 50:10. The mixture was mechanically milled using a ball mill to prepare the Li2S-SE-CNF composite. The milling conditions were 25 ℃ and 600 rpm for 10 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-SE-CNF composite was used as a composite cathode active material.
[0268] Comparative Example 13: Li2S-LiI-CNF, 600 rpm, 2 hr, 1 stage, 20 G
[0269] Li2S, LiI, and carbon nanofibers (CNF) were mixed in a weight ratio of 30:20:10. The mixture was mechanically milled using a ball mill to prepare a Li2S-LiI-CNF composite. The milling conditions were 25°C and 600 rpm for 2 hours. The milling energy applied to the sample during milling was 20 G. The Li2S-LiI-CNF composite was used as a composite cathode active material.
[0271] (Manufacturing of the anode)
[0272] Example 1: Al current collector / adhesive binder layer (polydopamine binder layer) / containing Li2S-LiI-C, PTFE dry anode
[0273] delete
[0274] A composition for forming a polydopamine layer was prepared by mixing 0.1g of dopamine with 50ml of a buffer solution with a pH of 8.5, and diluted by adding ethanol to improve viscosity and drying characteristics without affecting the pH during the process. The composition was spray-coated onto an aluminum foil serving as an anode current collector through a nozzle and dried at approximately 25°C to form a polydopamine layer with a thickness of approximately 10nm on the anode current collector.
[0275] As the cathode active material, the Li2S-LiI-CNF composite prepared in Preparation Example 4 was prepared. As the solid electrolyte, Li6PS5Cl, an argyrodite-type crystal (D50=3.0 μm, crystalline), was prepared. As the binder, PTFE was prepared.
[0276] The Li2S-LiI-CNF composite and the sulfide-based solid electrolyte were placed in a mixer and mixed for 2 minutes.
[0277] PTFE was added to the above-mentioned mixed product and mixed with a mixer for 20 seconds, and then the obtained anode mixture powder was kneaded and rolled with a roller to a thickness of 100 to 150 μm to manufacture an anode.
[0278] An anode mixture was prepared by mixing the above composite anode active material : solid electrolyte : adhesive binder (PTFE) in a weight ratio of 60 : 39 : 1.0. The anode mixture was obtained by dry mixing using a ball mill. The content of the adhesive binder, PTFE, is 500 parts by weight based on 100 parts by weight of polydopamine in the adhesive binder layer.
[0279] A dry anode was prepared by placing the anode composite onto an aluminum foil having an adhesive binder layer and plate pressing it at a pressure of 200 MPa for 10 minutes. The thickness of the anode was approximately 120 μm. The thickness of the anode active material layer was approximately 100 μm, and the thickness of the aluminum foil was approximately 20 μm. The area of the anode active material layer and the anode current collector were the same.
[0280] Example 2: Al current collector / adhesive binder layer (PAA binder layer) / containing Li2S-LiI-C, PTFE dry anode
[0281] delete
[0282] An anode was manufactured in the same manner as in Example 1, except that an adhesive binder layer using lithium polyacrylate (Li-PAA) was formed as follows.
[0283] First, an aqueous solution of lithium polyacrylate is prepared by adding 5 g of polyacrylic acid and 3.03 g of LiOH to 127.5 g of deionized water and mixing, then stirring at room temperature (25℃) for 24 hours to obtain 4 wt% of lithium polyacrylate (weight-average molecular weight: 450×10⁻⁶). 3 An aqueous solution containing ) was obtained.
[0284] An aqueous solution of lithium polyacrylate was applied onto aluminum foil and dried at 100°C to form an adhesive binder layer with a thickness of approximately 1 μm.
[0285] Example 3 (Al current collector / adhesive binder layer (polydopamine layer) / Li 2 S-LiI-C, containing PVDF Dry anode)
[0286] An anode was prepared in the same manner as in Example 1, except that PVDF was used instead of PTFE as the adhesive binder when preparing the anode mixture.
[0287] Example 4 (Al current collector / adhesive binder layer (polydopamine layer) / Li 2 S-LiI-C, containing PVDF Dry anode)
[0288] An anode was prepared in the same manner as in Example 2, except that PVDF was used instead of PTFE as the adhesive binder when preparing the anode mixture.
[0289] Example 5 (Al current collector / adhesive binder layer (polydopamine binder layer) / Li 2 S-LiI-C, PTFE content dry anode )
[0290] A cathode was prepared in the same manner as in Example 1, except that the weight ratio of the composite cathode active material: solid electrolyte: adhesive binder (PTFE) was changed to 60:37:3.0 when preparing the cathode composite.
[0291] Comparative Example 1: Al total / Li 2 Contains S-LiI-C complex dry anode
[0292] An anode was manufactured in the same manner as in Example 1, except that aluminum foil was used instead of aluminum foil with an adhesive binder layer.
[0293] Comparative Example 2: Al current collector containing a simple mixture of Li2S, LiI, and CNF dry anode
[0294] A cathode was prepared in the same manner as in Example 1, except that a simple mixture of Li2S, LiI, and CNF prepared in Comparative Example 2 was used instead of the Li2S-LiI-C composite prepared in Preparation Example 4.
[0295] Comparative Example 3: Al current collector / polydopamine layer / carbon coating layer / Li 2 S-LiI-C content anode
[0296] An anode was manufactured in the same manner as in Example 1, except that a carbon coating layer was formed on top of the polydopamine layer according to the following process.
[0297] A carbon coating layer composition was prepared by dispersing multilayer carbon nanotubes in an N-methyl-2-pyrrolidone solution in which 10 wt% of polyvinylidene fluoride binder was dissolved. In the carbon coating layer composition, the content of multilayer carbon nanotubes was 10 wt%, the content of NMP was 80 wt%, and the content of binder was 10 wt%. This was applied to the surface of a polydopamine layer and dried at a temperature of 120°C for 4 hours to form a carbon coating layer with a thickness of approximately 100 nm on the polydopamine layer.
[0298] delete
[0299] Reference Example 1: Positive current collector / Polydopamine layer / Polyne active material layer / SE / Ag / C negative layer
[0300] An anode was manufactured in the same manner as in Example 1, except that an adhesive binder layer was formed on the upper part of the aluminum foil as follows and an anode active material layer using an anode composite was formed on the upper part of the adhesive binder layer.
[0301] A composition for forming a polydopamine layer was prepared by mixing 0.1g of dopamine with 50ml of a pH 8.5 buffer solution, and diluted with ethanol to improve viscosity and drying characteristics without affecting the pH during the process. The composition was spray-coated onto the surface of aluminum foil through a nozzle and dried at approximately 25°C to form a polydopamine coating layer with a thickness of approximately 10nm, thereby forming a structure in which an anode current collector, a polydopamine layer, and an anode active material layer are laminated.
[0303] (Manufacturing of solid-state secondary batteries)
[0304] Example 6: Al current collector / adhesive binder layer / Li2S-LiI-C containing Dry Anode / / Sulfide-based Solid Electrolyte (SE) / / Ag-C coated SUS
[0305] (Anode manufacturing)
[0306] The anode of Example 1 was used.
[0307] (Cathode manufacturing)
[0308] A SUS foil with a thickness of 10 μm was prepared as a negative electrode current collector. As negative electrode active materials, carbon black (CB) with a primary particle size of about 30 nm and silver (Ag) particles with an average particle diameter of about 60 nm were prepared.
[0309] 4 g of a mixed powder, prepared by mixing carbon black (CB) and silver (Ag) particles in a weight ratio of 3:1, was placed in a container, and 4 g of an NMP solution containing 7 wt% of a PVDF binder (Kureha # 9300) was added to prepare a mixed solution. A slurry was prepared by stirring the mixed solution while gradually adding NMP to it. The prepared slurry was applied to a SUS sheet using a bar coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-roll-pressed to flatten the surface to prepare a cathode having a first cathode active material layer / cathode current collector structure. The thickness of the first cathode active material layer was approximately 15 μm. The area of the first cathode active material layer and the cathode current collector were the same.
[0310] (Preparation of solid electrolyte layer)
[0311] Li6PS5Cl solid electrolyte, an argyrodite-type crystal (D 50 A mixture was prepared by adding 1.5 parts by weight of an acrylic binder to 98.5 parts by weight of a solid electrolyte (=3.0 μm, crystalline). A slurry was prepared by stirring while adding octyl acetate to the prepared mixture. The prepared slurry was applied using a bar coater onto a 15 μm thick nonwoven fabric placed on a 75 μm thick PET substrate, and a laminate was prepared by drying in air at 80°C for 10 minutes. A solid electrolyte layer was prepared by vacuum drying the prepared laminate at 80°C for 2 hours.
[0312] (Inert component)
[0313] A flame-retardant inert member was manufactured by mixing cellulose fiber, glass fiber, aluminum hydroxide (Al(OH)3), an acrylic binder, and a solvent, forming the mixture into a gasket shape, and then removing the solvent.
[0314] The weight ratio of cellulose fiber, glass fiber, aluminum hydroxide (Al(OH)3), and acrylic binder was 20:8:70:2. The thickness of the inert material was 120 μm.
[0315] Before placing the manufactured flame-retardant inert material on the solid electrolyte layer, vacuum heat treatment was performed at 80°C for 5 hours to remove moisture and other substances from the flame-retardant inert material.
[0316] (Manufacturing of solid-state secondary batteries)
[0317] Referring to FIG. 4, a solid electrolyte layer was placed on the cathode such that a first cathode active material layer contacted the solid electrolyte layer, and an anode was placed on the solid electrolyte layer. A laminate was prepared by placing a gasket around the anode and in contact with the solid electrolyte layer. The thickness of the gasket was approximately 120 μm. The flame-retardant inert material was used as the gasket. The gasket was placed so as to contact the side of the anode and the solid electrolyte layer. The anode was placed in the center of the solid electrolyte layer, and the gasket was placed surrounding the anode and extending to the end of the solid electrolyte layer. The area of the anode was approximately 90% of the area of the solid electrolyte layer, and the gasket was placed over the entire remaining 10% of the area of the solid electrolyte layer where the anode was not placed.
[0318] The prepared laminate is 85 oPlate press treatment was performed at a pressure of 500 MPa for 30 min at C. This pressurization treatment sintered the solid electrolyte layer, thereby improving battery characteristics. The thickness of the sintered solid electrolyte layer was approximately 45 μm. The density of the Li6PS5Cl solid electrolyte, an argyrodite-type crystal contained in the sintered solid electrolyte layer, was 1.6 g / cc. The area of the solid electrolyte layer was equal to the area of the negative electrode.
[0319] A solid-state secondary battery was manufactured by placing a pressurized laminate into a pouch and vacuum sealing it. Parts of the positive and negative current collectors were extended outside the sealed battery to be used as the positive and negative terminals.
[0320] Examples 7 to 10
[0321] A solid secondary battery was manufactured in the same manner as in Example 6, except that the positive electrodes prepared in Examples 2 to 5 were each used.
[0322] Comparative Examples 4 to 6
[0323] A solid secondary battery was manufactured in the same manner as in Example 6, except that the positive electrodes prepared in Comparative Examples 1 to 3 were each used.
[0324] Reference Example 2
[0325] A solid secondary battery was manufactured in the same manner as in Example 6, except that the anode prepared in Reference Example 1 was used instead of the anode of Example 1.
[0327] Evaluation Example 1: XRD Analysis and Scanning Electron Microscopy Analysis
[0328] XRD spectra were measured using Cu Kα radiation for the bare Li2S used in Preparation Example 1, ground Li2S, and the Li2S-LiI-C composite prepared in Preparation Example 4. The measurement results are shown in Table 1 below.
[0329] The Li2S crystallite size and lattice constant were derived from the first peak for the (111) crystal plane appearing at a diffraction angle 2θ = 27° ± 2.0° in the XRD spectrum.
[0330] The ground Li2S was prepared by milling under the same conditions, except that the 50:30:20 weight ratio mixture of Li2S, LiI, and CNF used in Preparation Example 4 was changed to 100 parts by weight of Li2S.
[0331] For the bare Li2S used in Preparation Example 1, pulverized Li2S, and the Li2S-LiI-C composite prepared in Preparation Example 4, the particle size of the composite (i.e., D50 particle size) was measured using a laser particle size analyzer (PSA), and the Li2S particle size of the composite was measured using a scanning electron microscope. The measurement results are shown in Table 1 below.
[0332] division Li2S crystallite size [nm] Li2S particle size [㎛] bare Li2S 65 8 Crushed Li2S 15 - Li2S-LiI-C complex Less than 10 Less than 1
[0333] As shown in Table 1, the particle size and crystallite size of the Li2S-LiI-CNF composite were significantly reduced compared to Li2S. The Li2S-LiI-CNF composite contains a Li2S-LiI solid solution, the size of the Li2S crystallites is less than 9.9 nm, and the size of the Li2S particles in the composite is 2 μm or less.
[0334] Although not shown in Table 1, the lattice constant of the Li2S-LiI-CNF composite of Preparation Example 1 was greater than that of bare Li2S. The increase in the lattice constant of the Li2S-LiI-CNF composite compared to that of bare Li2S was determined to be due to the dissolution of LiI within the Li2S crystal. Therefore, it was confirmed that the Li2S-LiI-CNF composite forms a solid solution.
[0335] Although not shown in Table 1, the particle size of the Li2S-LiI-CNF composite of Preparation Example 1 was approximately 5 μm.
[0336] Evaluation Example 2: XRD Analysis and Scanning Electron Microscopy Analysis
[0337] XRD spectra were measured using Cu Kα radiation for the composite cathode active materials (i.e., composites) prepared in Preparation Examples 4 to 7 and Comparative Preparation Examples 3 to 13. The Li2S crystallite size calculated from the first peak corresponding to the (111) crystal plane appearing at the diffraction angle 2θ = 27° ± 2.0° in the measured XRD spectra is shown in Table 2 below. The crystallite size was calculated using the Sherrer Equation.
[0338] The Li2S particle size of the composite cathode active materials prepared in Preparation Examples 4 to 7 and Comparative Preparation Examples 3 to 13 was measured using a scanning electron microscope. The Li2S particle size of the composite cathode active material is the arithmetic mean of the particle sizes of multiple Li2S particles measured using software from the scanning electron microscope images. The measurement results are shown in Table 2 below.
[0339] division Stage 1 Milling 2nd stage milling Solid solution formation Li2S crystallite size [nm] Li2S particle size [㎛] Preparation Example 4 (28 G, 10 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 10 hr 600 rpm, 28 G, 10 hr ○ 9.8 Less than 1 Preparation Example 5 (28 G, 8 hr) (Li2S-LiI-CNF complex) 600 rpm, 28 G, 8 hr 600 rpm, 28 G, 8 hr ○ 7.2 Less than 1 Preparation Example 6 (28 G, 6 hr) (Li2S-LiI-CNF complex) 600 rpm, 28 G, 6 hr 600 rpm, 28 G, 6 hr ○ 8.2 Less than 1 Preparation Example 7 (28 G, 4 hr) (Li2S-LiI-CNF complex) 600 rpm, 28 G, 4 hr 600 rpm, 28 G, 4 hr ○ 9.5 Less than 1 Comparative Preparation Example 3 (28 G, 1 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 1 hr 600 rpm, 28 G, 1 hr ○ 20.1 Less than 1 Comparative Manufacturing Example 4 (28 G, 20 hr) (Li2S-LiI-CNF composite) 600 rpm, 28 G, 20 hr 600 rpm, 28 G, 20 hr △ 11.8 Less than 1 Comparative Manufacturing Example 5 (Li2S-LiI-CNF composite) 510 rpm, 20 G, 10 hr 510 rpm, 20 G, 10 hr ○ 9.9 Less than 1 Comparative Preparation Example 6 (7 G, 10 hr) (Li2S-LiI-CNF composite) 300 rpm, 7 G, 10 hr 300 rpm, 7 G, 10 hr × 27.2 3 Comparative Manufacturing Example 7 (38G, 10 hr) (Li2S-LiI-CNF composite) 700 rpm, 38 G, 10 hr 700 rpm, 38 G, 10 hr △ 15.6 2 Comparative Manufacturing Example 8 (0 G) (Li2S + CNF simple mixture) - - × 66.67 8 Comparative Manufacturing Example 9 (28 G, 1 hr) (Li2S-CNF composite) 600 rpm, 20 G, 2 hr - × 24.07 3 Comparative Manufacturing Example 10 (28 G, 10 hr) (Li2S-CNF composite) 600 rpm, 20 G, 10 hr - × 9.89 Less than 1 Comparative Preparation Example 11 (28 G, 10 hr) (Li2S-CNF-LiI composite) 600 rpm, 28 G, 10 hr 600 rpm, 28 G, 10 hr × 15.2 2 Comparative Manufacturing Example 12 (28 G, 10 hr) (Li2S-SE-CNF complex) 600 rpm, 28 G, 10 hr 600 rpm, 28 G, 10 hr × 8.9 Less than 1 Comparative Preparation Example 13 (28 G, 2 hr) (Li2S-LiI-CNF composite) 600 rpm, 20 G, 2 hr - ○ 22 3
[0340] As shown in Table 2, the Li2S-LiI-CNF composites of Preparation Examples 4 to 7 contain a Li2S-LiI solid solution, the size of the Li2S crystallites is less than 9.9 nm, and the size of the Li2S particles of the composite is 2 μm or less.
[0341] The Li2S-LiI-CNF composite of Comparative Example 3 had a size of Li2S crystallites greater than 9.9 nm as the milling energy was reduced during manufacturing.
[0342] In the Li2S-LiI-CNF composite of Comparative Example 4, as the milling energy increased during manufacturing, LiI phase-separated into a separate phase and failed to form a solid solution, and the size of the Li2S crystallites also increased.
[0343] The Li2S-LiI-CNF composite of Comparative Example 6 failed to form a Li2S-LiI solid solution because the milling energy was excessively reduced during manufacturing.
[0344] In the Li2S-LiI-CNF composite of Comparative Example 7, the Li2S-LiI solid solution was not properly formed due to the heat generated by the increased milling energy during manufacturing.
[0345] The Li2S-LiI-CNF composite of Comparative Example 13 is prepared in the first step, so it contains a Li2S-LiI solid solution, but the Li2S crystallite size increases and the Li2S particle size of the composite exceeds 2 μm.
[0346] The simple mixture of Li2S and CNF of Comparative Example 8, and the composites of Comparative Examples 9, 10, and 12 did not form a solid solution.
[0347] In the Li2S-CNF-LiI composite of Comparative Manufacturing Example 11, the Li2S-LiI solid solution was not properly formed because the Li2S-CNF composite was manufactured in the first step and then the Li2S-CNF-LiI composite was manufactured in the second step.
[0348] Evaluation Example 3: Charge / Discharge Test
[0349] The charge-discharge characteristics of the solid secondary batteries prepared in Examples 6-10, Comparative Examples 4-6, and Reference Example 2 were evaluated by the following charge-discharge test.
[0350] The charge / discharge test was performed by placing the solid secondary battery in a constant temperature bath at 45°C.
[0351] The first cycle involved charging at a constant current of 0.05 C for 20 hours until the battery voltage reached 2.8 V. Subsequently, discharging was performed at a constant current of 0.05 C for 20 hours until the battery voltage reached 1.0 V.
[0352] The second cycle was carried out by charging and discharging under the same conditions as the first cycle.
[0353] The second cycle discharge capacity was set to the standard capacity.
[0354] The third cycle involved charging at a constant current of 0.1 C for 10 hours until the battery voltage reached 2.8 V. Subsequently, discharging was performed at a constant current of 0.1 C for 10 hours until the battery voltage reached 1.0 V.
[0355] After the third cycle, charge and discharge were performed up to 50 cycles under the same conditions as the third cycle. The measurement results are shown in Table 3 below.
[0356] The initial efficiency is expressed by Equation 1 below, and the capacity retention rate is expressed by Equation 2 below.
[0357] <Equation 1>
[0358] Initial efficiency [%] = [1st cycle discharge capacity / 1st cycle charge capacity] × 100
[0359] <Equation 2>
[0360] Capacity Retention Rate (%) = [23rd Cycle Discharge Capacity / 3rd Cycle Discharge Capacity] × 100
[0361] division 0.05C discharge capacity (mAh / g) Initial efficiency (%) Dose retention rate (%) (20 times) Example 6 (Al current collector / adhesive binder layer (polydopamine layer) / Li2S-LiI-C, PTFE containing Dry anode) 911 78.8 90.5 Example 7 (Al current collector / adhesive binder layer (PAA binder layer) / Li2S-LiI-C, PTFE containing Dry anode) 922 79.2 91.9 Example 8 (Al current collector / adhesive binder layer (polydopamine layer) / Li2S-LiI-C, PVDF containing Dry anode) 918 81.1 89.2 Example 9 (Al current collector / adhesive binder layer (PAA binder layer) / Li2S-LiI-C, PVDF containing Dry anode) 927 83.6 91.7 Example 10 (Al current collector / adhesive binder layer (polydopamine layer) / Li2S-LiI-C, PTFE containing Dry anode) 883 85.2 94.7 Comparative Example 4 (containing Al current collector / Li2S-LiI-C complex) Dry anode) 709 72.6 59.1 Comparative Example 5 (containing Al current collector / simple mixture of Li2S, LiI, and CNF) Dry anode) 322 56.4 79.2 Comparative Example 6 (Al current collector / polydopamine layer / carbon layer / containing Li2S-LiI-C) anode) 868 80.2 81.2 Reference Example 2 (Polyode current collector / Polydopamine layer / Polyode active material layer) 576 73.2 70.2
[0362] As shown in Table 3, the solid secondary batteries of Examples 6 to 10 employing the cathodes of Examples 1 to 5 exhibited improved lifespan characteristics compared to the solid secondary batteries of Comparative Examples 4 to 6 employing the cathodes of Comparative Examples 1 to 3 and the solid secondary battery of Reference Example 2. The solid secondary batteries of Examples 8-9 having a polydopamine layer or Example 10 containing LiPAA showed improved discharge capacity due to enhanced adhesion between the cathode current collector and the cathode active material layer. Furthermore, even when charge and discharge cycles are repeated during cycling, stable contact between the cathode current collector and the cathode active material layer is maintained without detachment of the cathode active material, thereby improving the capacity retention rate.
[0363] Although not shown in the drawings, it was confirmed that a lithium metal layer, which is a second negative electrode active material layer, is formed between the first negative electrode active material layer and the negative electrode current collector after initial charging in the solid secondary batteries of Examples 6 to 10. This was confirmed through a cross-sectional scanning electron microscope image of the solid secondary battery. In addition, it was confirmed that a Li2S-LiI-CNF composite is disposed in the voids between a plurality of sulfide-based solid electrolyte particles in a scanning electron microscope image of the cross-section of the solid electrolyte layer.
[0364] Evaluation Example 4: Evaluation of Rate-Capability Characteristics
[0365] The rate capability characteristics of the solid secondary batteries of Examples 6 to 10, Comparative Examples 4 to 6, and Reference Example 2 were evaluated by the following charge-discharge test. The charge-discharge test was performed by placing the solid secondary batteries in a constant temperature bath at 45°C.
[0366] The first cycle involved charging at a constant current of 0.05 C for 20 hours until the battery voltage reached 2.8 V. Subsequently, discharging was performed at a constant current of 0.05 C for 20 hours until the battery voltage reached 1.0 V.
[0367] The second cycle was carried out by charging and discharging under the same conditions as the first cycle.
[0368] The third cycle involved charging at a constant current of 0.1 C for 10 hours until the battery voltage reached 2.8 V. Subsequently, the battery was discharged at a constant current of 0.1 C for 10 hours until the battery voltage reached 1.0 V. The fourth cycle involved charging and discharging under the same conditions as the third cycle.
[0369] In all charge / discharge cycles, a 10-minute pause was observed after each charge / discharge cycle. Some of the results of the room temperature charge / discharge experiments are shown in Table 4 below. The rate capability is defined by Equation 3 below.
[0370] <Equation 3>
[0371] Rate capability [%] = [Discharge capacity in 4th cycle / Discharge capacity in 2nd cycle] Х 100
[0372] division Rate capability (0.1C / 0.05C) Example 6 (Al current collector / adhesive binder layer (polydopamine layer) / Li2S-LiI-C, PTFE containing Dry anode) 96.2 Example 7 (Al current collector / adhesive binder layer (PAA binder layer) / Li2S-LiI-C, PTFE containing Dry anode) 95.8 Example 8 (Al current collector / adhesive binder layer (polydopamine layer) / Li2S-LiI-C, PVDF containing Dry anode) 94.8 Example 9 (Al current collector / adhesive binder layer (PAA binder layer) / Li2S-LiI-C, PVDF containing Dry anode) 94.2 Example 10 (Al current collector / adhesive binder layer (polydopamine layer) / Li2S-LiI-C, PTFE containing Dry anode) 93.6 Comparative Example 4 (containing Al current collector / Li2S-LiI-C complex) Dry anode) 80.5 Comparative Example 5 (containing Al current collector / simple mixture of Li2S, LiI, and CNF) Dry anode) 56.3 Comparative Example 6 (Al current collector / polydopamine layer / carbon layer / containing Li2S-LiI-C) anode) 93.2 Reference Example 2 (Polyode current collector / Polydopamine layer / Polyode active material layer) 84.2
[0373] As shown in Table 4, the solid secondary batteries of Examples 6 to 10 had improved rate capability compared to the solid secondary batteries prepared in Comparative Examples 4 to 6 and Reference Example 2. Explanation of the symbols
[0375] 1 Solid-state secondary battery 10 Positive electrode 11 Positive current collector 12 Positive active material layer 20 Negative electrode 21 Negative current collector 22 First negative active material layer 23 Thin film 24 Second negative active material layer 30 Electrolyte layer 40 Inert component
Claims
Claim 1 A positive current collector; an adhesive binder layer located on the positive current collector and containing an adhesive polymer; a positive active material layer located on the adhesive binder layer and containing a composite positive active material and a cohesion binder, wherein the composite positive active material comprises a Li2S-containing composite, the adhesive polymer is one or more selected from polydopamine, cation-substituted polycarboxylic acid, cation-substituted polycarboxylic acid copolymer, and polynorepinephrine, and the cohesion binder comprises polytetrafluoroethylene, polyvinylidene fluoride (PVdF)-based resin, styrene-butadiene rubber (SBR), polyethylene glycol (PEG), polypropylene glycol (PPG), and toluene diisocyanate (TDI). Polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan,A positive electrode for a solid-state secondary battery, which is carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, or a combination thereof. Claim 2 delete Claim 3 A positive electrode for a solid secondary battery according to claim 1, wherein the thickness of the adhesive binder layer is 5 nm to 1 μm. Claim 4 A positive electrode for a solid secondary battery according to claim 1, wherein the content of the adhesive binder is 1 to 10 parts by weight based on 100 parts by weight of the total weight of the positive electrode active material layer, and the content of the adhesive binder is 100 to 1000 parts by weight based on 100 parts by weight of the adhesive polymer of the adhesive binder layer. Claim 5 In claim 1, the Li2S-containing composite comprises a composite of Li2S and a lithium salt; and the composite of Li2S and the lithium salt comprises Li2S-Li a X b A positive electrode for a solid secondary battery, denoted as (1≤a≤5, 1≤b≤5), wherein X is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF6, BF4, SbF6, AsF6, ClO4, AlO2, AlCl4, NO3, CO3, BH4, SO4, BO3, PO4, NCl, NCl2, BN2, or a combination thereof. Claim 6 A positive electrode for a solid secondary battery according to claim 5, wherein the Li2S-containing composite further comprises a carbon-based material, the carbon-based material comprises a fibrous carbon-based material, the fibrous carbon-based material comprises a carbon nanostructure, the carbon nanostructure comprises a carbon nanofiber, a carbon nanotube, a carbon nanobelt, a carbon nanorod, or a combination thereof, and the content of the carbon-based material is 1 to 20 wt% of the total weight of the composite. Claim 7 A positive electrode for a solid secondary battery according to claim 5, wherein the lithium salt is a binary compound or a ternary compound, and the binary compound comprises LiI, LiBr, LiCl, LiF, LiH, Li2O, Li2Se, Li2Te, Li3N, Li3P, Li3As, Li3Sb, Li3Al2, LiB3 or a combination thereof, and the ternary compound comprises Li3OCl, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiNO3, Li2CO3, LiBH4, Li2SO4, Li3BO3, Li3PO4, Li4NCl, Li5NCl2, Li3BN2 or a combination thereof. Claim 8 A positive electrode for a solid secondary battery according to claim 1, wherein the Li2S-containing composite comprises a solid solution of Li2S and a lithium salt, the size of the composite particles is 10 μm or less, and the size of the Li2S crystallites obtained from the XRD spectrum of the composite is 20 nm or less. Claim 9 A positive electrode for a solid secondary battery according to claim 1, wherein the content of the adhesive binder in the positive electrode active material layer is 1 to 10 parts by weight based on 100 parts by weight of the total weight of the positive electrode active material layer. Claim 10 A positive electrode for a solid secondary battery according to claim 1, wherein the Li2S content in the composite is higher than the lithium salt content, and the molar ratio of Li2S to lithium salt in the composite is 51:49 to 95:
5. Claim 11 A positive electrode for a solid secondary battery according to claim 1, wherein the content of the composite is 60 to 80 wt% of the total weight of the positive electrode active material layer. Claim 12 In claim 1, the positive electrode active material layer further comprises a solid electrolyte, and the solid electrolyte comprises a sulfide-based solid electrolyte, forming a positive electrode for a solid secondary battery. Claim 13 In claim 12, the sulfide-based solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiX, where X is a halogen element, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , m, n are positive numbers, Z is one of Ge, Zn, or Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , p, q are positive numbers, M is one of P, Si, Ge, B, Al, Ga, In, Li 7-x PS 6-x Cl x , 0≤x≤2, Li 7-x PS 6-x Br x , 0≤x≤2, and Li 7-x PS 6-x I x A positive electrode for a solid secondary battery, one or more selected from , 0≤x≤2. Claim 14 A solid secondary battery comprising: a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises a positive electrode according to any one of claims 1, 3 to 13. Claim 15 A solid secondary battery according to claim 14, wherein the negative electrode comprises a negative electrode current collector and a first negative electrode active material layer disposed on one surface of the negative electrode current collector. Claim 16 A solid secondary battery according to claim 15, wherein the first negative electrode active material layer is a metal layer and the metal layer comprises lithium or a lithium alloy, or the first negative electrode active material layer comprises a negative electrode active material and a binder, wherein the negative electrode active material has a particle form and the average particle size of the negative electrode active material is 4 μm or less. Claim 17 A solid secondary battery according to claim 16, wherein the negative electrode active material comprises one or more selected from a carbon-based negative electrode active material and a metal or metalloid negative electrode active material, wherein the carbon-based negative electrode active material comprises amorphous carbon, crystalline carbon, porous carbon, or a combination thereof, and the metal or metalloid negative electrode active material comprises gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), or a combination thereof. Claim 18 A solid secondary battery according to claim 15, further comprising a second negative active material layer disposed between the negative current collector and the first negative active material layer and between the negative current collector and the electrolyte layer, wherein the second negative active material layer is a metal layer and the metal layer comprises lithium or a lithium alloy. Claim 19 A solid secondary battery according to claim 14, wherein the solid electrolyte layer comprises an oxide-based solid electrolyte, a polymer solid electrolyte, a gel electrolyte, or a combination thereof, and the gel electrolyte comprises a polymer gel electrolyte. Claim 20 A solid secondary battery according to claim 14, wherein the positive electrode comprises a positive current collector and the negative electrode comprises a negative current collector, and one or more of the positive current collector and the negative current collector comprise a base film and a metal layer disposed on one or both sides of the base film, wherein the base film comprises a polymer, and the polymer comprises polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof, and the metal layer comprises indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. Claim 21 A positive electrode for a solid secondary battery according to claim 12, wherein the sulfide-based solid electrolyte comprises an argyrodite-type solid electrolyte, wherein the argyrodite-type solid electrolyte comprises one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I, wherein the density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc, and the sulfide-based solid electrolyte is in the form of particles, and the average particle size (D50) of the particles is 0.1 μm to 1.9 μm. Claim 22 A positive electrode for a solid secondary battery according to claim 1, wherein the cation-substituted polycarboxylic acid is one or more selected from lithium polyacrylate (LiPAA) and lithium polymethacrylate, and the cation-substituted polycarboxylic acid copolymer is a lithium (acrylic acid-co-maleic acid) salt, or a lithium (methyl vinyl ether-alt-maleic acid) salt, or a lithium (butadiene-co-maleic acid) salt. Claim 23 A solid secondary battery according to claim 16, wherein the negative electrode active material comprises a mixture of a first particle made of amorphous carbon and a second particle made of a metal or metalloid, and the content of the second particle is 1 to 60 wt% based on the total weight of the mixture.
Citation Information
Patent Citations
All solid secondary battery and all solid secondary battery structure
EP4086983A2
Solid battery
KR102093337B1
Positive electrode for all-solid secondary battery, method for manufacturing same, and all-solid secondary battery
US20170317337A1